Bacteriostatic high-barrier nanocellulose-based composite film for fresh keeping of fruits and vegetables and preparation method of bacteriostatic high-barrier nanocellulose-based composite film

Through sulfonation and quaternization modification treatment of nanocellulose, combined with silver-loaded chitosan and intercalated montmorillonite, a nanocellulose-based composite film with excellent barrier, antibacterial and mechanical properties was prepared, which solved the shortcomings of existing fruit and vegetable plastic wraps in terms of barrier performance, breathability and antibacterial effects, and achieved efficient fresh preservation and environmentally friendly packaging of fruits and vegetables.

CN119552397AInactive Publication Date: 2025-03-04中科纳美(天津)生物工程有限公司 +2

Patent Information

Application Number
CN202510127045.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-28
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing fruit and vegetable plastic wrap has shortcomings in barrier properties, breathability and antibacterial effects, resulting in fruits and vegetables being perishable during storage and potential risks to the environment and human health.

Method used

Nanocellulose was treated with sulfonated and quaternized modification, combined with silver-carrying chitosan and intercalated montmorillonite, and nanocellulose-based composite films with excellent barrier, antibacterial and mechanical properties were prepared.

Benefits of technology

It significantly improves the barrier properties, antibacterial properties and mechanical properties of fruit and vegetable plastic wrap, extends the shelf life of fruit and vegetable, reduces food waste and losses, and improves the environmental protection and safety of the materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552397A_ABST
    Figure CN119552397A_ABST
Patent Text Reader

Abstract

The invention provides a bacteriostatic high-barrier nano-cellulose-based composite film for fruit and vegetable preservation and a preparation method thereof, and the preparation method comprises the following steps: carrying out sulfonation modification treatment on nano-cellulose powder by using 1, 3-propane sultone to obtain sulfonated nano-cellulose; then, octadecyl trimethyl ammonium chloride is adopted for conducting quaternization modification treatment on the sulfonated nano-crystalline cellulose, and quaternary ammonium sulfonated nano-crystalline cellulose is obtained; the preparation method comprises the following steps: dispersing silver-loaded chitosan in deionized water to obtain a silver-loaded chitosan solution, adding montmorillonite into the silver-loaded chitosan solution, mixing, stirring and heating, and then carrying out suction filtration, washing and drying to obtain intercalated montmorillonite; the preparation method comprises the following steps: uniformly mixing polylactic acid, quaternary ammonium sulfonated nano-cellulose, intercalated montmorillonite, a plasticizer, a lubricant and an antioxidant to obtain a mixed material, and sequentially carrying out melt extrusion, cooling, pelletizing and film blowing on the mixed material to obtain the antibacterial high-barrier nano-cellulose-based composite film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fruit and vegetable preservation, and relates to an antibacterial high-barrier nano-cellulose-based composite film for fruit and vegetable preservation and a preparation method thereof. Background Art

[0002] Fruit and vegetable fresh-keeping film is an important part of the food packaging field. Its main function is to extend the shelf life of fruits and vegetables, reduce losses during storage and transportation, and maintain the quality and nutritional value of fruits and vegetables. Traditional fruit and vegetable fresh-keeping films are mostly made of materials such as polyethylene (PE), polyvinyl chloride (PVC) and polypropylene (PP). Although these materials have a certain fresh-keeping effect, they are non-degradable and cause environmental pollution. With the improvement of consumers' awareness of food safety and environmental protection, the development of new environmentally friendly and efficient fruit and vegetable fresh-keeping films has become a hot topic in current research.

[0003] At present, there are many kinds of fruit and vegetable cling films on the market, but they generally have the problem of insufficient air permeability and fresh-keeping performance. For example, although some cling films can prevent the intrusion of external moisture, they have poor air permeability, which leads to the inability to discharge the carbon dioxide produced by fruits and vegetables during storage in time, accelerating the aging and decay of fruits and vegetables. In addition, although some cling films are added with antibacterial agents, the antibacterial effect is limited and may have adverse effects on the fruits and vegetables themselves. Therefore, it is particularly important to develop a fruit and vegetable cling film that has both excellent barrier properties and good air permeability and antibacterial effects.

[0004] As a new type of bio-based functional material, nanocellulose has the characteristics of light weight, high strength, high specific surface area, extremely low thermal expansion coefficient, excellent weather resistance, good biocompatibility and degradability, and has shown great application potential in the field of food packaging. A large number of hydroxyl groups are exposed on the surface of nanocellulose, which makes it have great potential for chemical modification. Nanocellulose-based composite materials with specific functions can be prepared through chemical modification, physical treatment and other methods.

[0005] In recent years, the application of nanocellulose in fruit and vegetable cling film has gradually attracted attention. Studies have shown that adding nanocellulose to cling film can significantly improve the barrier properties and mechanical properties of the cling film, while giving the cling film good antibacterial properties. The addition of nanocellulose can also improve the air permeability of the cling film, so that the carbon dioxide and oxygen produced by fruits and vegetables during storage can be effectively regulated, thereby extending the shelf life of fruits and vegetables.

[0006] However, the application of nanocellulose in fruit and vegetable preservation films is still in its infancy, with problems such as poor barrier properties, weak antibacterial effects, and unstable performance. Therefore, developing a method for preparing a nanocellulose-based composite film with high barrier and high antibacterial efficiency is of great significance for promoting the application of nanocellulose in the field of fruit and vegetable preservation. Summary of the invention

[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables and a preparation method thereof. The composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables and reduce food waste and loss.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables, the preparation method comprising:

[0010] (I) sulfonating and modifying nanocellulose powder with 1,3-propane sultone to obtain sulfonated nanocellulose; then quaternizing and modifying the sulfonated nanocellulose with octadecyltrimethylammonium chloride to obtain quaternary ammonium sulfonated nanocellulose;

[0011] (II) ball-milling chitosan powder and sodium hydroxide to obtain a mixture, adding sodium chloroacetate and sodium iodide to the mixture for a second ball-milling to obtain carboxymethyl chitosan; then, quaternizing the carboxymethyl chitosan with dimethyl diallyl ammonium chloride to obtain quaternized carboxymethyl chitosan;

[0012] (III) dispersing the quaternized carboxymethyl chitosan obtained in step (II) in deionized water to obtain a chitosan solution, dripping a silver ammonia solution into the chitosan solution under stirring and water bath heating conditions, and continuing to mix, stir and heat to react after all the silver ammonia solution has been dripped in, and then dialyzing and freeze-drying to obtain silver-loaded chitosan;

[0013] (IV) dispersing the silver-loaded chitosan obtained in step (III) in deionized water to obtain a silver-loaded chitosan solution, adding montmorillonite to the silver-loaded chitosan solution, mixing, stirring and heating, and then filtering, washing and drying to obtain intercalated montmorillonite;

[0014] (V) Polylactic acid, the quaternary ammonium sulfonated nanocellulose obtained in step (I), the intercalated montmorillonite obtained in step (IV), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixture, and the mixture is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the antibacterial high-barrier nanocellulose-based composite film.

[0015] The antibacterial high-barrier nanocellulose-based composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties, and has great application potential in the field of fruit and vegetable preservation. First, the present invention improves its dispersibility and compatibility in the polymer matrix by sulfonation and quaternization modification of nanocellulose, thereby enhancing the mechanical properties and barrier properties of the composite film. Secondly, silver-loaded chitosan can destroy the cell structure of bacteria and interfere with its metabolic process, thereby effectively inhibiting the growth of common food spoilage bacteria such as Escherichia coli and Staphylococcus aureus. At the same time, silver ions have broad-spectrum antibacterial properties and are not easy to produce drug resistance, giving the composite film excellent antibacterial properties, effectively extending the shelf life of fruits and vegetables. In addition, quaternary ammonium sulfonated nanocellulose and quaternary ammonium carboxymethyl chitosan form a more compact network structure in the composite film, improve the tensile strength, tear strength and toughness of the composite film, and the mechanical properties, which enable the composite film to better protect fruits and vegetables during packaging, transportation, etc., and reduce damage and deformation caused by external forces. Thirdly, the intercalation modification of montmorillonite by silver-loaded chitosan improves the dispersibility of montmorillonite in the polymer matrix, and the addition of intercalated montmorillonite further improves the barrier properties of the composite film, forming a denser and more effective barrier, and reducing the penetration of oxygen, water, etc. through the composite film. The composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables and reduce food waste and loss.

[0016] Nanocellulose is one of the most abundant natural polymers. It has the advantages of wide source, renewable, biodegradable, good biocompatibility and green environmental protection. In addition, it has excellent mechanical properties, high specific surface area, low density and good thermal stability. It is an excellent nano-reinforced filler. The tensile strength, elastic modulus, thermal stability and barrier properties of the composite film can be significantly improved by adding nanocellulose to the polymer matrix. However, there are a large number of hydroxyl functional groups on the surface of nanocellulose, which hinders its compatibility and dispersibility in the polymer matrix and limits the further enhancement of the performance of the composite film. Therefore, it is necessary to hydrophobically modify nanocellulose and reduce its hydrophilicity, so as to improve the compatibility and dispersibility of nanocellulose in the polymer matrix. In addition, in order to give the composite film excellent antibacterial properties, it is necessary to consider the compatibility of the antibacterial agent in the composite material system to avoid the negative impact of the addition of the antibacterial agent on the performance of the composite film.

[0017] In order to solve the problem that the dispersibility of hydrophilic nanocellulose in the hydrophobic polymer matrix and the lack of antibacterial activity of nanocellulose, the present invention adopts sulfonation and quaternary ammonium salt adsorption combined modification to process nanocellulose, so that the surface properties of nanocellulose are optimized, not only the hydrophilicity of nanocellulose is reduced, but also its compatibility and dispersibility with the polymer matrix are improved, and more polar functional groups are introduced, which is conducive to forming stronger interfacial interaction. At the same time, the modified nanocellulose also gives the composite film excellent antibacterial properties and mechanical properties, and the quaternary ammonium sulfonated nanocellulose forms a continuous network structure in the composite film, which effectively improves the tensile strength and toughness of the composite film.

[0018] Among the numerous organic antimicrobial modifiers, quaternary ammonium antimicrobial agents have the advantages of broad-spectrum antimicrobial activity, low toxicity, low price, and good environmental stability. The bactericidal mechanism is as follows: the quaternary ammonium cationic functional group adsorbs the negatively charged bacterial cell membrane on the surface through electrostatic action, and then the long alkane chain of the quaternary ammonium salt enters the phospholipid bilayer of the cell membrane, interfering with the normal metabolism of the bacterial cells, and ultimately leading to bacterial cell lysis to achieve the bactericidal and antibacterial effects. Due to the electrostatic adsorption mechanism of quaternary ammonium salts in the antibacterial process, it can widely act on the negatively charged bacterial surface rather than specifically bind to kill bacteria, and thus can effectively avoid the risk of increased bacterial resistance.

[0019] Since polymer quaternary ammonium salts have more action sites and higher charge density, they are more conducive to the electrostatic adsorption effect, and the adsorption effect between bacteria is faster and stronger; however, too large a molecular weight will also affect the contact of quaternary ammonium salt molecules with the bacterial surface to play a role, which will lead to a weakening of antibacterial activity. The present invention uses octadecyl trimethyl ammonium chloride as an organic antibacterial agent, and uses physical electrostatic adsorption to load octadecyl trimethyl ammonium chloride onto nanocellulose, while satisfying the hydrophobic modification and antibacterial modification of nanocellulose. However, the loading amount of nanocellulose on octadecyl trimethyl ammonium chloride depends on the anion content on its surface. In order to increase the loading amount of octadecyl trimethyl ammonium chloride, the present invention first sulfonates the nanocellulose by 1,3-propane sultone. The sulfonation modification can provide rich and stable anion sites for the surface of nanocellulose, which is conducive to improving the adsorption of nanocellulose on octadecyl trimethyl ammonium chloride.

[0020] The invention sequentially performs carboxymethyl modification and quaternization modification on chitosan to obtain quaternized carboxymethyl chitosan, then uses silver ammonia solution as a precursor and quaternized carboxymethyl chitosan as a reducing agent and a stabilizer to prepare silver-loaded chitosan; finally, the silver-loaded chitosan is used to perform intercalation modification on montmorillonite, and after ion exchange between organic cations of dimethyl diallyl ammonium chloride grafted on the silver-loaded chitosan and inorganic cations between montmorillonite layers, the cations are partially attached to the montmorillonite sheets, and the organic cations are transferred to the montmorillonite sheets. Some of them stay in the interlayer. As the chitosan molecular chain enters the interlayer of montmorillonite, the interlayer distance of montmorillonite increases, the structure becomes looser, the porosity is higher, and some layers are peeled off, so that the silver-loaded chitosan is fixedly loaded between the layers of montmorillonite. This structure not only maintains the original barrier properties of montmorillonite, but also enhances the barrier capacity of the material to gases (such as oxygen, carbon dioxide) and water through the interaction of chitosan molecular chains, which can effectively extend the shelf life of food and prevent moisture from invading and causing the performance of the material to deteriorate. In addition, the introduction of silver-loaded chitosan also improves the thermal and chemical stability of montmorillonite. The functional groups in the chitosan molecular chain can form hydrogen bonds with the hydroxyl groups on the surface of montmorillonite, which enhances the interlayer interaction force and makes the intercalation structure more stable. At the same time, the presence of silver nanoparticles also plays a catalytic stabilizing role, further improving the overall stability of the intercalated montmorillonite. This improvement in stability enables the intercalated montmorillonite to maintain good barrier properties under extreme environmental conditions (such as high temperature and high humidity).

[0021] Chitosan is mainly composed of random copolymerization of N-acetylglucosamine and glucosamine units. The particularity of this structure gives chitosan a series of significant functional properties, such as excellent biocompatibility, non-toxicity, good biodegradability and antibacterial activity, but unmodified chitosan is only water-soluble and antibacterial under acidic conditions, which limits its scope of application. The present invention uses sodium chloroacetate to carboxymethylate chitosan, aiming to introduce hydrophilic carboxymethyl functional groups, thereby improving the water solubility and reactivity of chitosan. Compared with chitosan, carboxymethyl chitosan not only retains the original biocompatibility and degradability of chitosan, but also gives it certain antibacterial and reactivity, laying the foundation for subsequent quaternary ammonium modification; at the same time, the chain structure of carboxymethyl chitosan is more flexible, the concentration of chelating groups is larger, and its ability to chelate metal particles is stronger than chitosan, so it can be used as a reducing agent and stabilizer for subsequent silver nanoparticles.

[0022] The present invention uses sodium chloroacetate as a carboxymethyl modification agent and sodium iodide as a catalyst, and adopts a mechanochemical method to induce a chemical reaction, thereby introducing a carboxymethyl functional group on the chitosan molecular chain, and the introduction of the carboxymethyl functional group greatly improves the solubility of chitosan. The present invention adopts mechanical ball milling to promote the alkalization reaction and the carboxymethylation reaction. During the ball milling process, the ball milling medium and the reaction material are subjected to the combined force of rotation and revolution in the ball mill, so that the centrifugal acceleration of the ball milling medium can reach 10-20g; at the same time, the pressure between the ball milling medium and the ball mill can reach 5-6 times of the weight of the ball milling medium itself. When the chitosan molecule is subjected to a strong mechanical force of the ball milling medium, the impact force and shear force of the chitosan particles will destroy the crystal structure in the molecule. During the ball milling alkalization process, sodium hydroxide can better enter the interior of the chitosan molecule, thereby achieving the effect of alkalization expansion. At the same time, during the carboxymethylation reaction, as the hydrogen bonds within and between chitosan molecules are broken by external mechanical force, the hydroxyl and amino groups within the chitosan molecules are exposed to the outside, thereby providing an attack target for the carboxymethyl groups in the system and promoting the occurrence of the carboxymethylation reaction.

[0023] In addition to the carboxymethyl functional group, the carboxymethyl chitosan also has free hydroxyl groups and amino groups that are not completely reacted during the carboxymethylation of the chitosan, so that the carboxymethyl chitosan has enough reactive functional groups. On this basis, the present invention adopts dimethyl diallyl ammonium chloride to perform quaternization modification on the carboxymethyl chitosan. The quaternization modification not only retains and improves the water solubility of the carboxymethyl chitosan, but also grafts quaternary ammonium salt cations on the carboxymethyl chitosan molecular chain through the graft copolymerization reaction of dimethyl diallyl ammonium chloride and carboxymethyl chitosan. On the one hand, the water solubility of the chitosan can be further improved. The quaternary ammonium functional group is grafted into the chitosan molecular chain through the graft copolymerization reaction. The introduction of the quaternary ammonium functional group weakens the hydrogen bonding effect in the chitosan molecule, destroys its crystal structure, and increases the distance between the molecular chains. The molecules are in a "loose" state, which is conducive to the approach and penetration of water molecules. Therefore, chitosan modified with quaternary ammonium salts can be dissolved under both acidic and alkaline conditions, and the solution has good stability, does not change color or degrade; on the other hand, quaternary ammonium modification not only improves the water solubility of chitosan, but also significantly enhances its antibacterial properties. The quaternary ammonium functional group carries a stronger positive charge, which can interact with the negative charge on the surface of bacterial cells, destroy the integrity of the bacterial cell wall, and cause bacterial death; in addition, the high charge density of the quaternary ammonium modified chitosan enables it to form a polycationic electrolyte, which reacts with the acidic macromolecules produced on the surface of bacterial cells to form a polyelectrolyte complex, further inhibiting the growth of bacteria.

[0024] The present invention particularly preferably uses dimethyldiallyl ammonium chloride to quaternize carboxymethyl chitosan. The dimethyldiallyl ammonium chloride copolymer belongs to an organic cation. In the subsequent montmorillonite intercalation modification process, the dimethyldiallyl ammonium chloride copolymer can exchange cations with inorganic cations between montmorillonite layers to enter the interlayers of montmorillonite and open the interlayers of montmorillonite. The montmorillonite with enlarged interlayer spacing is used as a carrier of silver-loaded chitosan to achieve load fixation of the silver-loaded chitosan, and can effectively prevent the agglomeration of the silver-loaded chitosan and silver nanoparticles loaded between the interlayers.

[0025] Silver nanoparticles have excellent antibacterial properties and have obvious inhibitory effects on various microorganisms such as bacteria and fungi. Its antibacterial mechanism involves destroying cell membrane permeability, affecting bacterial cell phospholipid and protein synthesis, etc., and can effectively kill or inhibit the growth of pathogens. Compared with traditional antibiotics, silver nanoparticles are not easy to cause microorganisms to develop drug resistance, which enables silver-loaded chitosan to maintain a stable antibacterial effect in long-term use. The present invention uses quaternized carboxymethyl chitosan to coat and fix silver nanoparticles, further enhancing the application efficiency and safety of silver nanoparticles. On the one hand, quaternized carboxymethyl chitosan can form a smooth, transparent, flexible and breathable film, which helps to prevent the penetration and growth of microorganisms, and synergizes with silver nanoparticles to significantly improve the antibacterial effect. At the same time, the carboxymethyl functional groups on the quaternized carboxymethyl chitosan molecular chain can also chelate with metal ions, further enhancing its antibacterial ability. On the other hand, although silver nanoparticles have excellent antibacterial properties, their potential cytotoxicity limits their direct application. The present invention uses quaternized carboxymethyl chitosan to coat silver nanoparticles, which can effectively reduce the cytotoxicity of silver nanoparticles and improve their biosafety; at the same time, through the coating of quaternized carboxymethyl chitosan, the slow release of silver ions can be achieved, the antibacterial action time can be extended, and the stability of silver nanoparticles can be improved, preventing their aggregation and precipitation, and maintaining long-term antibacterial activity.

[0026] As a layered silicate mineral, intercalated montmorillonite has extremely high specific surface area and interlayer adsorption capacity. Through the intercalation modification of silver-loaded chitosan, the interlayer spacing of montmorillonite is expanded and the interlayer structure is effectively regulated. This intercalation structure not only improves the dispersion uniformity of intercalated montmorillonite in the composite film, but also enhances its interfacial bonding force with the polymer matrix. At the same time, intercalated montmorillonite, as an inorganic nanofiller, can significantly enhance the rigidity and heat resistance of the composite film.

[0027] In the composite film, the synergistic effect between quaternary ammonium sulfonated nanocellulose and intercalated montmorillonite is mainly reflected in the following aspects:

[0028] On the one hand, the two can significantly improve the mechanical strength of the composite film through synergistic enhancement. The network structure formed by quaternary ammonium sulfonated nanocellulose and the inorganic nano-filling effect of intercalated montmorillonite are superimposed on each other to form a denser and tougher film structure. This structure enables the composite film to more effectively disperse and transfer stress when subjected to external forces, thereby improving the tensile strength and tear resistance of the composite film.

[0029] On the other hand, the two can significantly improve the barrier properties of the composite film through synergistic enhancement. Both quaternary ammonium sulfonated nanocellulose and intercalated montmorillonite have excellent barrier properties. The close arrangement of quaternary ammonium sulfonated nanocellulose and the interlayer adsorption of intercalated montmorillonite together form an effective barrier that can significantly block the penetration of small molecules such as gas and water. In addition, the silver nanoparticles loaded in the intercalated montmorillonite layer also have antibacterial properties, which can further extend the shelf life of fruits and vegetables.

[0030] As a preferred technical solution of the present invention, in step (I), the sulfonated nanocellulose is prepared by the following method:

[0031] The nanocellulose powder is added into a sodium hydroxide solution, and a nanocellulose dispersion is obtained after ultrasonic dispersion, and then the nanocellulose dispersion is mixed, stirred and heated to obtain a nanocellulose suspension; a 1,3-propane sultone solution is added into the nanocellulose suspension, and the mixture is mixed, stirred and heated to react, and a reaction product is obtained after the reaction is completed, and a hydrochloric acid solution is dripped into the reaction product to adjust its pH value, and then the reaction product is dialyzed and freeze-dried to obtain the sulfonated nanocellulose.

[0032] In some optional examples, the mass fraction of the sodium hydroxide solution is 5-10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the ratio of the nanocellulose powder to the sodium hydroxide solution is 1g:(50~60)mL, for example, it can be 1g:50mL, 1g:51mL, 1g:52mL, 1g:53mL, 1g:54mL, 1g:55mL, 1g:56mL, 1g:57mL, 1g:58mL, 1g:59mL or 1g:60mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the nanocellulose powder and the sodium hydroxide solution is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the ultrasonic dispersion time of the nanocellulose powder and the sodium hydroxide solution is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional examples, the mixing and stirring time of the nanocellulose dispersion is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] In some optional examples, the heating temperature during mixing and stirring of the nanocellulose dispersion is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional examples, the 1,3-propane sultone solution consists of 1,3-propane sultone and dimethyl sulfoxide.

[0039] In some optional examples, the mass fraction of 1,3-propane sultone in the 1,3-propane sultone solution is 4-5wt%, for example, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt% or 5.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0040] In some optional examples, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone is 1:(0.14~0.15), for example, it can be 1:0.14, 1:0.141, 1:0.142, 1:0.143, 1:0.144, 1:0.145, 1:0.146, 1:0.147, 1:0.148, 1:0.149 or 1:0.15, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0041] The present invention particularly limits the mass ratio of nanocellulose powder to 1,3-propane sultone in the nanocellulose suspension to 1:(0.14-0.15). When the amount of 1,3-propane sultone used is lower than the lower limit of the range defined by the present invention, the number of sulfonic acid functional groups on the surface of the nanocellulose is too small, and the sulfonation modification is insufficient, thereby affecting the number of anion sites on the surface of the nanocellulose, resulting in a decrease in its adsorption capacity for octadecyltrimethylammonium chloride; in addition, the sulfonic acid functional groups serve as molecular bridges connecting the nanocellulose and octadecyltrimethylammonium chloride, and their insufficient number will directly affect the effect of quaternary ammonium modification, resulting in uneven distribution of octadecyltrimethylammonium chloride on the surface of the nanocellulose and a decrease in the grafting rate, which ultimately affects the antibacterial and mechanical properties of the quaternary ammonium sulfonated nanocellulose.

[0042] When the amount of 1,3-propane sultone exceeds the upper limit of the range defined by the present invention, it will cause excessive sulfonation of nanocellulose, causing significant changes in the chemical structure and physical properties of sulfonated nanocellulose, and the chain structure of sulfonated nanocellulose will break due to excessive reaction, resulting in a decrease in its strength, rigidity and stability. In addition, excessive sulfonation will also affect the subsequent quaternization modification effect, because, on the one hand, the sulfonic acid functional groups on the surface of sulfonated nanocellulose are limited in number as adsorption sites, and when the amount of 1,3-propane sultone is increased, although more sulfonic acid functional groups are introduced, the excessive amount of 1,3-propane sultone will lead to saturation of adsorption sites, and the part exceeding the carrying capacity of the surface of sulfonated nanocellulose will not be able to effectively participate in the subsequent quaternization reaction. On the other hand, during the quaternization process, octadecyltrimethylammonium chloride needs to be adsorbed on the sulfonic acid functional groups on the surface of sulfonated nanocellulose. When the dosage of 1,3-propane sultone is too high, it will lead to uneven distribution of sulfonic acid functional groups, which will in turn cause uneven distribution of octadecyltrimethylammonium chloride on the surface of sulfonated nanocellulose, affecting the performance of the final product.

[0043] In some optional examples, the mixing and stirring time of the nanocellulose suspension and 1,3-propane sultone is 5 to 6 hours, for example, it can be 5.0 hours, 5.1 hours, 5.2 hours, 5.3 hours, 5.4 hours, 5.5 hours, 5.6 hours, 5.7 hours, 5.8 hours, 5.9 hours or 6.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0044] In some optional examples, the heating temperature when the nanocellulose suspension is mixed and stirred with 1,3-propane sultone is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In some optional instances, the mass fraction of the hydrochloric acid solution is 5~10wt%, for example, it can be 5.0wt%, 5.5wt%, 6.0wt%, 6.5wt%, 7.0wt%, 7.5wt%, 8.0wt%, 8.5wt%, 9.0wt%, 9.5wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional embodiments, hydrochloric acid solution is added dropwise to the reaction product to adjust its pH value to 1-2, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] In some optional examples, the dialysis time is 2 to 3 days.

[0049] In some optional embodiments, the freeze-drying temperature is -60~-70°C, for example, it can be -60°C, -61°C, -62°C, -63°C, -64°C, -65°C, -66°C, -67°C, -68°C, -69°C or -70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the freeze-drying time is 6 to 12 hours, for example, it can be 6.0 h, 6.5 h, 7.0 h, 7.5 h, 8.0 h, 8.5 h, 9.0 h, 9.5 h, 10.0 h, 10.5 h, 11.0 h, 11.5 h or 12.0 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] As a preferred technical solution of the present invention, in step (I), the quaternary ammonium sulfonated nanocellulose is prepared by the following method:

[0052] The sulfonated nanocellulose is added to isopropanol to obtain a sulfonated nanocellulose suspension after ultrasonic dispersion, an alkali solution is added dropwise to the sulfonated nanocellulose suspension to adjust its pH value, and then octadecyltrimethylammonium chloride is added to the sulfonated nanocellulose suspension, mixed and stirred and heated for a period of time, and then the heating is stopped, and the mixing and stirring is continued at room temperature for a period of time to obtain a reaction product, and the reaction product is dialyzed and freeze-dried to obtain the quaternary ammonium sulfonated nanocellulose.

[0053] The presence of isopropanol can increase the disorder of sulfonated nanocellulose and reduce the possibility of hydrogen bond formation and cross-linking, so that the sulfonated nanocellulose maintains a larger specific surface area, which is beneficial to the quaternary ammonium cationic modification reaction of sulfonated nanocellulose. At the same time, the use of isopropanol can destroy the crystal structure of sulfonated nanocellulose to a large extent, so that the quaternary ammonium modification reaction can proceed more fully.

[0054] In some optional examples, the ratio of the sulfonated nanocellulose to isopropanol is 1g:(30~40)mL, for example, it can be 1g:30mL, 1g:31mL, 1g:32mL, 1g:33mL, 1g:34mL, 1g:35mL, 1g:36mL, 1g:37mL, 1g:38mL, 1g:39mL or 1g:40mL, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In some optional examples, the ultrasonic power of the ultrasonic dispersion of the sulfonated nanocellulose and isopropanol is 300-400 W, for example, 300 W, 310 W, 320 W, 330 W, 340 W, 350 W, 360 W, 370 W, 380 W, 390 W or 400 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0056] In some optional examples, the ultrasonic dispersion time of the sulfonated nanocellulose and isopropanol is 30 to 40 min, for example, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] In some optional examples, the concentration of the alkali solution is 0.5~1.5mol / L, for example, it can be 0.5mol / L, 0.6mol / L, 0.7mol / L, 0.8mol / L, 0.9mol / L, 1.0mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L or 1.5mol / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In some optional embodiments, an alkali solution is added to the sulfonated nanocellulose suspension to adjust its pH value to 9-10, for example, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0059] In some optional examples, the mass ratio of the sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is 1:(0.2~0.3), for example, it can be 1:0.2, 1:0.21, 1:0.22, 1:0.23, 1:0.24, 1:0.25, 1:0.26, 1:0.27, 1:0.28, 1:0.29 or 1:0.3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0060] The present invention particularly limits the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension to 1:(0.2-0.3). When the amount of octadecyltrimethylammonium chloride used is lower than the lower limit of the range defined by the present invention, the coverage of octadecyltrimethylammonium chloride on the surface of sulfonated nanocellulose is insufficient. The antibacterial effect of octadecyltrimethylammonium chloride mainly depends on the interaction between its positive charge and the negative charge of the bacterial cell membrane, thereby destroying the integrity of the bacterial cell membrane. If the coverage of octadecyltrimethylammonium chloride is insufficient, the chance of octadecyltrimethylammonium chloride contacting with the bacterial cell membrane is reduced, resulting in decreased antibacterial performance of the product. In addition, as a cationic surfactant, octadecyltrimethylammonium chloride has a significant hydrophobic property in its long-chain alkyl part. When octadecyltrimethylammonium chloride is combined with sulfonated nanocellulose, the hydrophobic alkyl chains of the quaternary ammonium salt tend to be arranged in a direction away from water molecules, thereby forming a hydrophobic barrier on the surface of nanocellulose. This barrier can effectively prevent the penetration of water molecules and improve the hydrophobic properties of the material. When the amount of octadecyltrimethylammonium chloride is too small, the number of hydrophobic alkyl chains is limited and a complete hydrophobic barrier cannot be formed, resulting in insufficient hydrophobicity of the product, which in turn affects its compatibility and dispersibility with the polylactic acid matrix.

[0061] However, increasing the amount of octadecyltrimethylammonium chloride can increase the positive charge density on the surface of the sulfonated nanocellulose, thereby enhancing the antibacterial properties of the product. However, when the amount of octadecyltrimethylammonium chloride exceeds the upper limit of the range defined in the present invention, the hydrophobic modification of the surface of the sulfonated nanocellulose is close to saturation, and further increasing the amount of octadecyltrimethylammonium chloride cannot further increase the number of hydrophobic alkyl chains. Instead, it may cause the product surface to be too rough or form an uneven hydrophobic layer, affecting the overall performance of the product.

[0062] In some optional examples, the mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride is 3 to 4 hours, for example, it can be 3.0 hours, 3.1 hours, 3.2 hours, 3.3 hours, 3.4 hours, 3.5 hours, 3.6 hours, 3.7 hours, 3.8 hours, 3.9 hours or 4.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0063] In some optional examples, the heating temperature when the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred is 60-70°C, for example, it can be 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C or 70°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0064] In some optional examples, the mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride at room temperature is 10 to 15 hours, for example, it can be 10.0 hours, 10.5 hours, 11.0 hours, 11.5 hours, 12.0 hours, 12.5 hours, 13.0 hours, 13.5 hours, 14.0 hours, 14.5 hours or 15.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0065] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0066] In some optional examples, the dialysis time is 5 to 8 days, for example, 5 days, 6 days, 7 days or 8 days, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0067] In some optional embodiments, the freeze-drying temperature is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0068] In some optional embodiments, the freeze-drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0069] As a preferred technical solution of the present invention, in step (II), the mass ratio of the chitosan powder to sodium hydroxide is 1:(3.5-4.5), for example, it can be 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4 or 1:4.5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0070] The present invention particularly limits the mass ratio of chitosan powder and sodium hydroxide to 1:(3.5-4.5), and along with the increase of sodium hydroxide consumption, the substitution degree of the carboxymethyl functional group of the product obtained after subsequent carboxymethylation modification presents a variation trend of first increasing and then decreasing. In the alkalization reaction process, sodium hydroxide plays the role of alkalization expansion, and when the consumption of sodium hydroxide is lower than the lower limit of the range defined by the present invention, it does not have a good alkalization expansion effect, affects the subsequent carboxymethylation reaction, and causes the substitution degree of the carboxymethyl functional group of the product to be lower. Along with the increase of sodium hydroxide consumption, the active center formed also increases thereupon, the structure of chitosan is destroyed, and the particles expand, so that it can better react with sodium chloroacetate, so that the carboxymethylation reaction is fully carried out, and therefore, the substitution degree of the carboxymethyl functional group of the product is gradually improved. When the amount of sodium hydroxide used exceeds the upper limit of the range defined in the present invention, not only mass transfer is hindered, but also the excess sodium hydroxide will neutralize a portion of the sodium chloroacetate, affecting the progress of the carboxymethylation reaction, resulting in a decrease in the reaction efficiency of the carboxymethylation reaction. At the same time, since the generated by-products are wrapped in the surface layer of the chitosan, it is difficult for the sodium chloroacetate to contact the inside of the chitosan, which hinders the progress of the carboxymethylation reaction to a certain extent. Therefore, the degree of substitution of the carboxymethyl functional group of the product is reduced.

[0071] In some optional examples, the rotation speed of the primary ball milling is 500~600rpm, for example, it can be 500rpm, 510rpm, 520rpm, 530rpm, 540rpm, 550rpm, 560rpm, 570rpm, 580rpm, 590rpm or 600rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0072] In some optional examples, the time for the first ball milling is 4 to 5 hours, for example, it can be 4.0 hours, 4.1 hours, 4.2 hours, 4.3 hours, 4.4 hours, 4.5 hours, 4.6 hours, 4.7 hours, 4.8 hours, 4.9 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0073] In some optional examples, the mass ratio of the chitosan powder to sodium chloroacetate is 1:(3~4), for example, it can be 1:3.0, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9 or 1:4.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0074] The present invention particularly limits the mass ratio of chitosan powder and sodium chloroacetate to 1:(3-4), and with the increase of the sodium chloroacetate consumption, the substitution degree of the carboxymethyl functional group of the product presents a variation trend of first increasing and then decreasing. When the mass ratio of chitosan powder and sodium chloroacetate is within the numerical range defined by the present invention, with the increase of the sodium chloroacetate consumption, the probability of collision between the chitosan active center and the sodium chloroacetate increases, so that the carboxymethylation reaction is carried out in a positive direction, and therefore the substitution degree of the carboxymethyl functional group of the product is gradually improved. When the consumption of sodium chloroacetate exceeds the upper limit of the range defined by the present invention, excessive sodium chloroacetate consumes a part of sodium hydroxide, resulting in the occurrence of side reactions, reducing the utilization rate of sodium hydroxide, and causing the substitution degree of the carboxymethyl functional group of the product to decrease.

[0075] In some optional examples, the mass ratio of sodium chloroacetate to sodium iodide is 1:(0.5~0.7), for example, it can be 1:0.5, 1:0.52, 1:0.54, 1:0.56, 1:0.58, 1:0.6, 1:0.62, 1:0.64, 1:0.66, 1:0.68 or 1:0.7, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0076] In some optional examples, the rotation speed of the secondary ball milling is 500~600rpm, for example, it can be 500rpm, 510rpm, 520rpm, 530rpm, 540rpm, 550rpm, 560rpm, 570rpm, 580rpm, 590rpm or 600rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0077] The invention particularly limits the rotation speed of the secondary ball milling to 500-600 rpm, and as the rotation speed of the ball milling increases, the substitution degree of the carboxymethyl functional group of the product shows a trend of first increasing and then decreasing. When the rotation speed of the ball mill is within the range of 500-600 rpm, accelerating the rotation speed of the ball milling can increase the collision probability and the number of collisions of the chitosan powder, sodium hydroxide, sodium chloroacetate and sodium iodide, and when the mechanical force is large enough, the stress generated instantly by the chitosan powder far exceeds its mechanical strength, and then the powder particles are broken, the specific surface area is increased, the contact of the chitosan powder with the sodium hydroxide, sodium chloroacetate and sodium iodide is promoted, and the reaction rate of the carboxymethyl reaction is increased, so the substitution degree of the carboxymethyl functional group of the product is gradually increased. When the ball mill speed exceeds 600rpm, the excessively fast speed causes the contact time between the reaction materials and the ball milling medium to be too short. At the same time, the particle size of the chitosan powder cannot be further reduced after reaching the limit, and the tiny particles will agglomerate into secondary particles under the action of surface energy, van der Waals force and electrostatic force. When the ball mill speed exceeds 600rpm, the agglomeration rate of the tiny particles will exceed the generation rate of the tiny particles. At this time, a large number of secondary particles will be generated in the reaction system, resulting in a sharp decrease in the specific surface area of ​​the material and a rapid decrease in the reaction rate, which ultimately leads to a decrease in the degree of substitution of the carboxymethyl functional group of the product.

[0078] In some optional embodiments, the secondary ball milling time is 5 to 6 hours, for example, it can be 5.0h, 5.1h, 5.2h, 5.3h, 5.4h, 5.5h, 5.6h, 5.7h, 5.8h, 5.9h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0079] In some optional examples, the preparation process of the carboxymethyl chitosan further comprises:

[0080] After the secondary ball milling, a solid product is obtained, and the solid product is uniformly mixed with deionized water to obtain a product solution. A hydrochloric acid solution with a mass fraction of 8-10wt% is added to the product solution to adjust the pH value of the product solution to 7; then, the product solution is filtered, washed and dried to obtain the carboxymethyl chitosan, which can be, for example, 8.0wt%, 8.2wt%, 8.4wt%, 8.6wt%, 8.8wt%, 9.0wt%, 9.2wt%, 9.4wt%, 9.6wt%, 9.8wt% or 10.0wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0081] As a preferred technical solution of the present invention, in step (II), the quaternized carboxymethyl chitosan is prepared by the following method:

[0082] The carboxymethyl chitosan is dissolved in deionized water and mixed evenly to obtain a carboxymethyl chitosan solution; under continuous stirring and water bath heating conditions, a dimethyl diallyl ammonium chloride solution is added dropwise to the carboxymethyl chitosan solution, and after the dimethyl diallyl ammonium chloride solution is completely added dropwise, the mixture is continuously stirred and heated to obtain a reaction product; acetone is added to the reaction product, and white floccules are generated after mixing, and then the mixture is filtered, washed and dried to obtain the quaternized carboxymethyl chitosan.

[0083] In some optional examples, the concentration of carboxymethyl chitosan in the carboxymethyl chitosan solution is 10-20 g / L, for example, it can be 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] In some optional examples, the mass fraction of the dimethyldiallylammonium chloride solution is 50-60wt%, for example, it can be 50wt%, 51wt%, 52wt%, 53wt%, 54wt%, 55wt%, 56wt%, 57wt%, 58wt%, 59wt% or 60wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0085] In some optional examples, during the dropwise addition of the dimethyldiallylammonium chloride solution, the temperature of the water bath heating is 50-60°C, for example, 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0086] In some optional examples, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:(0.6~0.7), for example, it can be 1:0.6, 1:0.61, 1:0.62, 1:0.63, 1:0.64, 1:0.65, 1:0.66, 1:0.67, 1:0.68, 1:0.69 or 1:0.7, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0087] The present invention particularly defines that the mass ratio of carboxymethyl chitosan to dimethyl diallyl ammonium chloride is 1:(0.6-0.7), and with the increase of the amount of dimethyl diallyl ammonium chloride, the grafting rate of quaternization reaction shows a trend of increasing first and then decreasing, which is due to the fact that, within the numerical range defined by the present invention, the concentration of dimethyl diallyl ammonium chloride is increased, and the reaction system will produce a large number of active free radicals, thereby inducing a large number of grafting sites, so that the reaction efficiency of quaternization reaction is greatly improved. However, due to the large steric hindrance of dimethyl diallyl ammonium chloride, it is more inclined to copolymerization, therefore, when the concentration of dimethyl diallyl ammonium chloride is too high, the homopolymerization reaction of dimethyl diallyl ammonium chloride monomer will be accelerated, which hinders the occurrence of graft copolymerization between dimethyl diallyl ammonium chloride and carboxymethyl chitosan to a certain extent, thereby causing the grafting rate of quaternization reaction to decrease.

[0088] In some optional examples, after all the dimethyldiallylammonium chloride solution is added dropwise, mixing and stirring are continued under water bath heating conditions for 20 to 30 minutes, for example, 20 minutes, 21 minutes, 22 minutes, 23 minutes, 24 minutes, 25 minutes, 26 minutes, 27 minutes, 28 minutes, 29 minutes or 30 minutes, but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0089] In some optional examples, the volume ratio of the reaction product to the acetone is 1:(1-1.2), for example, 1:1.0, 1:1.02, 1:1.04, 1:1.06, 1:1.08, 1:1.1, 1:1.12, 1:1.14, 1:1.16, 1:1.18 or 1:1.2, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0090] As a preferred technical solution of the present invention, in step (III), the concentration of quaternized carboxymethyl chitosan in the chitosan solution is 10-20 g / L, for example, it can be 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0091] In some optional examples, the silver ammonia solution is prepared by the following method:

[0092] Under stirring conditions, sodium hydroxide solution is added to the silver nitrate solution to react and generate a silver oxide suspension containing a black silver oxide precipitate. Ammonia solution is added dropwise to the silver oxide suspension until the black silver oxide precipitate is completely dissolved to obtain a clear silver ammonia solution.

[0093] In some optional examples, the mass fraction of the silver nitrate solution is 3~5wt%, for example, it can be 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt%, 4.0wt%, 4.2wt%, 4.4wt%, 4.6wt%, 4.8wt% or 5.0wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0094] In some optional examples, the mass fraction of the sodium hydroxide solution is 2-4wt%, for example, it can be 2.0wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, 3.0wt%, 3.2wt%, 3.4wt%, 3.6wt%, 3.8wt% or 4.0wt%, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0095] In some optional examples, the mass ratio of silver nitrate in the silver nitrate solution to sodium hydroxide in the sodium hydroxide solution is 1:(0.5~0.8), for example, it can be 1:0.5, 1:0.55, 1:0.6, 1:0.65, 1:0.7, 1:0.75 or 1:0.8, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0096] In some optional examples, the concentration of the aqueous ammonia solution is 1~3wt%, for example, it can be 1.0wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt%, 2.0wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt% or 3.0wt%, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0097] In some optional examples, during the dropwise addition of the silver ammonia solution, the temperature of the water bath heating is 70-80°C, for example, 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C or 80°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0098] The present invention particularly limits the water bath heating temperature to 70-80°C. When the reaction temperature is lower than 70°C, the reduction rate of silver ions by quaternized carboxymethyl chitosan is low, and only a small amount of silver seeds grow into silver nanoparticles. As the temperature increases, on the one hand, the growth rate of silver seeds into silver nanoparticles is accelerated, and on the other hand, a large amount of silver ions in the mixed solution system form crystal nuclei, further generate silver nanoparticles, and increase the silver loading of the product. When the reaction temperature is higher than 80°C, the silver nanoparticles generated in the solution will continuously collide due to the intensification of Brownian motion, the silver nanoparticles will cluster, and a silver single substance with a larger particle size will be generated, which cannot be evenly loaded on the quaternized carboxymethyl chitosan, resulting in a decrease in the silver loading of the product.

[0099] In some optional examples, the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:(0.6~0.7), for example, it can be 1:0.6, 1:0.61, 1:0.62, 1:0.63, 1:0.64, 1:0.65, 1:0.66, 1:0.67, 1:0.68, 1:0.69 or 1:0.7, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0100] The present invention particularly limits the mass ratio of quaternized carboxymethyl chitosan to silver nitrate to 1:(0.6-0.7). When the amount of silver nitrate is lower than the lower limit of the range defined by the present invention, the number of silver nanoparticles generated on the quaternized carboxymethyl chitosan is small and unevenly distributed. As a broad-spectrum antibacterial agent, the antibacterial performance of the silver nanoparticles mainly depends on the interaction between the silver nanoparticles and the bacterial cell membrane, and the ability to interfere with the metabolic process of the bacteria after entering the interior of the bacteria. If the content of the silver nanoparticles is insufficient, the growth and reproduction of the bacteria cannot be effectively inhibited. In addition, the uneven distribution of the silver nanoparticles will lead to a lack of sufficient antibacterial effect in some areas. With the increase of the amount of silver nitrate, the generation amount of the silver nanoparticles gradually increases, and the antibacterial performance of the silver-loaded chitosan is significantly enhanced.

[0101] In addition, the amount of silver nitrate used will directly affect the particle size of the generated silver nanoparticles. The formation of silver nanoparticles includes two processes: nucleation and crystal growth. In the nucleation process, a certain degree of supersaturation is required to overcome the surface energy barrier. The crystal growth process is a process in which the newly reduced silver element is adsorbed on the surface of the original crystal nucleus and grows on the basis of the previous nucleation. Both processes will undergo liquid phase reduction reactions, but nucleation is the main process in the early stage and crystal growth is the main process in the later stage. In the nucleation process, the concentration of silver nanoparticles exceeds the critical concentration value, the system reaches a supersaturated state, and silver nanoparticles can precipitate from the reaction system. When the amount of silver nitrate is too small, the silver ion concentration is low, the supersaturation of silver nanoparticles is relatively low, the crystal nucleation rate is greater than the crystal growth rate, and the particle size of the generated silver nanoparticles is small. When the amount of silver nitrate is increased, the silver ion concentration in the reaction system increases, the supersaturation continues to increase, the crystal growth rate is greater than the crystal nucleation rate, and the particle size of the generated silver nanoparticles is larger.

[0102] Therefore, when the amount of silver nitrate used exceeds the upper limit of the range defined by the present invention, large-diameter silver nanoparticles will be formed. At the same time, unreacted silver ions gather on the surface of the silver nanoparticles and undergo a reduction reaction on the surface of the silver nanoparticles, so that the large-diameter silver nanoparticles are further agglomerated to generate secondary particles with a larger particle size but a smaller specific surface area. The secondary particles will affect the full contact between the silver nanoparticles and the bacteria, thereby affecting the full play of its antibacterial properties. When the amount of silver nitrate used is lower than the lower limit of the range defined by the present invention, small-diameter silver nanoparticles will be formed. Silver nanoparticles with too small a particle size will also agglomerate, resulting in a reduction in specific surface area. The present invention achieves the purpose of regulating the particle size of the silver nanoparticles by controlling the amount of silver nitrate used.

[0103] In some optional examples, after all the silver ammonia solution is dropped in, mixing and stirring is continued for 8 to 10 hours, for example, 8.0 hours, 8.2 hours, 8.4 hours, 8.6 hours, 8.8 hours, 9.0 hours, 9.2 hours, 9.4 hours, 9.6 hours, 9.8 hours or 10.0 hours, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0104] In some optional examples, the molecular weight cutoff of the dialysis bag used in the dialysis is 10,000~20,000Da, for example, it can be 10,000Da, 11,000Da, 12,000Da, 13,000Da, 14,000Da, 15,000Da, 16,000Da, 17,000Da, 18,000Da, 19,000Da or 20,000Da, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0105] In some optional examples, the dialysis time is 2 to 3 days.

[0106] In some optional embodiments, the freeze-drying temperature is -40~-50°C, for example, it can be -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0107] In some optional embodiments, the freeze-drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0108] As a preferred technical solution of the present invention, in step (IV), the concentration of silver-loaded chitosan in the silver-loaded chitosan solution is 10-20 g / L, for example, it can be 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L or 20 g / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0109] In some optional examples, the mass ratio of the silver-loaded chitosan in the silver-loaded chitosan solution to the montmorillonite is 1:(4-5), for example, 1:4.0, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5.0, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0110] The present invention specifically limits the mass ratio of silver-loaded chitosan to montmorillonite in the silver-loaded chitosan solution to 1:(4-5). When the amount of montmorillonite exceeds the upper limit of the range defined by the present invention, the amount of silver-loaded chitosan is relatively too low. Although montmorillonite, as an inorganic nanomaterial, has a certain adsorption capacity and layered structure, it does not have antibacterial properties. Therefore, too low an amount of silver-loaded chitosan will result in insufficient concentration of silver nanoparticles in the product, thereby weakening the antibacterial effect of the product; in addition, too much montmorillonite will also hinder the release and diffusion of silver nanoparticles to a certain extent, further reducing the antibacterial properties of the product; again, when the amount of silver-loaded chitosan is too low, the intercalation modification effect on montmorillonite is weak, and the interlamellar space of montmorillonite cannot be fully opened, thereby affecting the barrier properties of the product. When the amount of montmorillonite is lower than the lower limit of the range defined by the present invention, the amount of silver-loaded chitosan is relatively too high, and too much silver-loaded chitosan will make the product too viscous, affecting its subsequent processing performance and stability. In addition, excessive release of silver ions may pose potential risks to the environment and human health. Thirdly, too high a content of silver-loaded chitosan will cause the montmorillonite layers to be completely stretched and peeled off, which in turn causes the silver-loaded chitosan to be completely exposed, affecting the loading and fixing effect of montmorillonite on the silver-loaded chitosan.

[0111] In some optional examples, the mixing and stirring time of the silver-loaded chitosan solution and montmorillonite is 5 to 7 hours, for example, it can be 5.0 hours, 5.2 hours, 5.4 hours, 5.6 hours, 5.8 hours, 6.0 hours, 6.2 hours, 6.4 hours, 6.6 hours, 6.8 hours or 7.0 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0112] In some optional embodiments, the heating temperature when the silver-loaded chitosan solution and montmorillonite are mixed and stirred is 50-60°C, for example, it can be 50°C, 51°C, 52°C, 53°C, 54°C, 55°C, 56°C, 57°C, 58°C, 59°C or 60°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0113] As a preferred technical solution of the present invention, in step (V), the weight proportions of the components in the mixed material are as follows:

[0114] Polylactic acid 75-78 parts;

[0115] 8-10 parts of quaternary ammonium sulfonated nanocellulose;

[0116] Intercalated montmorillonite 12-14 parts;

[0117] 1~2 parts of plasticizer;

[0118] Lubricant 0.5~1.5 parts;

[0119] Antioxidant 0.1~0.5 parts.

[0120] Among them, the weight parts of polylactic acid can be 70 parts, 71 parts, 72 parts, 73 parts, 74 parts, 75 parts, 76 parts, 77 parts, 78 parts, 79 parts or 80 parts; the weight parts of quaternary ammonium sulfonated nanocellulose can be 5.0 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6.0 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, 7.0 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts or 8.0 parts; the weight parts of intercalated montmorillonite can be 12 parts, 12.5 parts, 13 parts, 13.5 parts, 14 parts, 14.5 parts or 15 parts; the weight parts of plasticizer can be The weight parts of the lubricant can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0 parts; the weight parts of the lubricant can be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4 or 1.5 parts; the weight parts of the antioxidant can be 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45 or 0.5 parts, but are not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0121] In some optional examples, the plasticizer includes any one of triacetin, tributyl citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, acetyl tributyl citrate, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof.

[0122] In some optional examples, the lubricant includes any one of paraffin, zinc stearate, calcium stearate, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof.

[0123] In some optional examples, the antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168 or antioxidant 691, or a combination of at least two thereof.

[0124] As a preferred technical solution of the present invention, in step (V), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction.

[0125] In some optional instances, the temperature of the first zone is 150-160°C, for example, it may be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0126] In some optional instances, the temperature of the second zone is 160-170°C, for example, it may be 160°C, 161°C, 162°C, 163°C, 164°C, 165°C, 166°C, 167°C, 168°C, 169°C or 170°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0127] In some optional instances, the temperature of the third zone is 170-180°C, for example, it may be 170°C, 171°C, 172°C, 173°C, 174°C, 175°C, 176°C, 177°C, 178°C, 179°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0128] In some optional instances, the temperature of the fourth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0129] In some optional examples, the temperature of the fifth zone is 185-190°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0130] In some optional examples, the temperature of the sixth zone is 190-195°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0131] In some optional examples, the temperature of the seventh zone is 200-205°C, for example, it can be 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0132] In some optional examples, the temperature of the eighth zone is 195-200°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0133] In some optional instances, the head temperature of the screw extruder is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0134] In some optional examples, the screw speed of the screw extruder is 200~300rpm, for example, it can be 200rpm, 210rpm, 220rpm, 230rpm, 240rpm, 250rpm, 260rpm, 270rpm, 280rpm, 290rpm or 300rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0135] In some optional examples, the film blowing process is carried out in a film blowing machine, and the interior of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction.

[0136] In some optional instances, the temperature of the ninth zone is 175-185°C, for example, it can be 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C or 185°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0137] In some optional instances, the temperature of the tenth zone is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0138] In some optional instances, the temperature of the eleventh zone is 185-195°C, for example, it can be 185°C, 186°C, 187°C, 188°C, 189°C, 190°C, 191°C, 192°C, 193°C, 194°C or 195°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0139] In some optional instances, the temperature of the twelfth zone is 195-205°C, for example, it can be 195°C, 196°C, 197°C, 198°C, 199°C, 200°C, 201°C, 202°C, 203°C, 204°C or 205°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0140] In some optional instances, the temperature of the thirteenth zone is 190-200°C, for example, it can be 190°C, 191°C, 192°C, 193°C, 194°C, 195°C, 196°C, 197°C, 198°C, 199°C or 200°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0141] In some optional examples, the screw speed of the film blowing machine is 100~200rpm, for example, it can be 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, 150rpm, 160rpm, 170rpm, 180rpm, 190rpm or 200rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0142] In some optional examples, the traction speed of the film blowing machine is 5~10m / min, for example, it can be 5.0m / min, 5.5m / min, 6.0m / min, 6.5m / min, 7.0m / min, 7.5m / min, 8.0m / min, 8.5m / min, 9.0m / min, 9.5m / min or 10.0m / min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0143] In some optional examples, the blowing ratio of the film blowing machine is 2 to 5, for example, 2, 3, 4 or 5, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0144] In a second aspect, the present invention provides an antibacterial high-barrier nano-cellulose-based composite film for preserving fruits and vegetables, which is prepared by the preparation method described in the first aspect, wherein the antibacterial high-barrier nano-cellulose-based composite film comprises polylactic acid, quaternary ammonium sulfonated nano-cellulose, intercalated montmorillonite, a plasticizer, a lubricant and an antioxidant.

[0145] Compared with the prior art, the present invention has the following beneficial effects:

[0146] The antibacterial high-barrier nanocellulose-based composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties, and has great application potential in the field of fruit and vegetable preservation. First, the present invention improves its dispersibility and compatibility in the polymer matrix by sulfonation and quaternization modification of nanocellulose, thereby enhancing the mechanical properties and barrier properties of the composite film. Secondly, silver-loaded chitosan can destroy the cell structure of bacteria and interfere with its metabolic process, thereby effectively inhibiting the growth of common food spoilage bacteria such as Escherichia coli and Staphylococcus aureus. At the same time, silver ions have broad-spectrum antibacterial properties and are not easy to produce drug resistance, giving the composite film excellent antibacterial properties, effectively extending the shelf life of fruits and vegetables. In addition, quaternary ammonium sulfonated nanocellulose and quaternary ammonium carboxymethyl chitosan form a more compact network structure in the composite film, improve the tensile strength, tear strength and toughness of the composite film, and the mechanical properties, which enable the composite film to better protect fruits and vegetables during packaging, transportation, etc., and reduce damage and deformation caused by external forces. Thirdly, the intercalation modification of montmorillonite by silver-loaded chitosan improves the dispersibility of montmorillonite in the polymer matrix, and the addition of intercalated montmorillonite further improves the barrier properties of the composite film, forming a denser and more effective barrier, and reducing the penetration of oxygen, water, etc. through the composite film. The composite film prepared by the present invention has excellent barrier properties, antibacterial properties and mechanical properties. Using it for fruit and vegetable packaging can significantly extend the shelf life of fruits and vegetables and reduce food waste and loss. BRIEF DESCRIPTION OF THE DRAWINGS

[0147] Figure 1 A process flow chart of the preparation of the composite film provided in Examples 1-5 of the present invention;

[0148] Figure 2 The infrared spectra of nanocellulose, sulfonated nanocellulose prepared in Example 1 of the present invention and quaternary ammonium sulfonated nanocellulose;

[0149] Figure 3 zeta potential diagrams of nanocellulose, sulfonated nanocellulose prepared in Example 1 of the present invention, and quaternary ammonium sulfonated nanocellulose;

[0150] Figure 4 This is the infrared spectrum of chitosan used in Example 1 of the present invention;

[0151] Figure 5 This is the infrared spectrum of the carboxymethyl chitosan prepared in Example 1 of the present invention;

[0152] Figure 6 This is the infrared spectrum of the quaternized carboxymethyl chitosan prepared in Example 1 of the present invention;

[0153] Figure 7This is a scanning electron microscope image of the chitosan used in Example 1 of the present invention;

[0154] Figure 8 This is a scanning electron microscope image of the quaternized carboxymethyl chitosan prepared in Example 1 of the present invention;

[0155] Fig. 9 This is a scanning electron microscope image of the silver-loaded chitosan prepared in Example 1 of the present invention;

[0156] Fig.10 This is a transmission electron microscope image of the montmorillonite used in Example 1 of the present invention;

[0157] Fig.11 This is a transmission electron microscope image of the intercalated montmorillonite prepared in Example 1 of the present invention;

[0158] Fig.12 XRD spectra of montmorillonite, silver-loaded chitosan prepared in Example 1 of the present invention, and intercalated montmorillonite;

[0159] Fig.13 This is a colony diagram obtained in the antibacterial performance test of Escherichia coli of the composite film prepared in the comparative example of the present invention;

[0160] Fig.14 This is a colony diagram obtained in the antibacterial performance test of Escherichia coli of the composite film prepared in Example 1 of the present invention;

[0161] Fig.15 This is a colony diagram obtained in a test of the antibacterial performance of Staphylococcus aureus of the composite film prepared in the comparative example of the present invention;

[0162] Fig.16 This is a colony diagram obtained in the antibacterial performance test of the composite film prepared in Example 1 of the present invention on Staphylococcus aureus;

[0163] Fig.17 The actual photos of the composite films prepared in Example 1 of the present invention and the comparative example taken in the green vegetable preservation experiment;

[0164] Fig.18 The following are actual photos of the composite films prepared in Example 1 of the present invention and the comparative example taken in a mango preservation experiment. DETAILED DESCRIPTION

[0165] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0166] Example 1

[0167] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0168] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 5 wt% (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:50 mL), and ultrasonically disperse the nanocellulose at an ultrasonic power of 300 W for 40 min to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 50 °C for 5 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 4 wt%, and add the mixture to the nanocellulose suspension. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.14, the mixture was mixed and stirred at 60°C for 6 hours, and a reaction product was obtained after the reaction was completed. A 5wt% hydrochloric acid solution was dripped into the reaction product to adjust its pH value to 2, and then the reaction product was dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 10000Da. After the dialysis was completed, the dialyzed product was placed at -60°C for freeze-drying for 12 hours to obtain sulfonated nanocellulose;

[0169] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:30 mL, and then ultrasonically dispersed for 40 min at an ultrasonic power of 300 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 0.5 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.2, and mixed and stirred at 60° C. for 4 h, and then heating was stopped, and mixed and stirred at room temperature for 15 h to obtain a reaction product, and then the reaction product was dialyzed for 5 days using a dialysis bag with a molecular weight cutoff of 10000 Da, and after the dialysis, the dialyzed product was freeze-dried at -40° C. for 24 h to obtain quaternary ammonium sulfonated nanocellulose;

[0170] (2) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:3.5, and ball-milled for 5 hours at a speed of 500 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.5, and ball-milled for a second time at a speed of 500 rpm for 6 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 8wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain the carboxymethyl chitosan;

[0171] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 10 g / L; add a 50 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 50° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.6, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 30 minutes under 50° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;

[0172] (3) under stirring conditions, adding a sodium hydroxide solution with a mass fraction of 2 wt% to a silver nitrate solution with a mass fraction of 3 wt%, wherein the mass ratio of silver nitrate in the silver nitrate solution to sodium hydroxide in the sodium hydroxide solution is 1:0.5, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 1 wt% dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;

[0173] The quaternized carboxymethyl chitosan obtained in step (2) is dispersed in deionized water to obtain a chitosan solution with a concentration of 10 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 70° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.6. After all the silver ammonia solution is dripped in, the mixture is stirred under heating in a water bath at 70° C. for 10 h. The reaction product is then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 10,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -40° C. for 24 h to obtain silver-loaded chitosan.

[0174] (4) dispersing the silver-loaded chitosan obtained in step (3) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 10 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4, mixing and stirring at 50° C. for 7 h, and then filtering, washing and drying to obtain intercalated montmorillonite;

[0175] (5) 75 parts of polylactic acid, 10 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 12 parts of intercalated montmorillonite obtained in step (4), 1 part of ethylene glycol, 1.5 parts of calcium stearate and 0.5 parts of antioxidant 1010 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 150° C., the temperature of the second zone is 160° C., the temperature of the third zone is 170° C., the temperature of the fourth zone is 175° C., the temperature of the fifth zone is 185° C., the temperature of the sixth zone is 190° C., the temperature of the seventh zone is 200° C., the temperature of the eighth zone is 195° C., the temperature of the die head is 180° C., and the screw speed is 200 rpm;

[0176] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 175°C, the temperature of the tenth zone is 180°C, the temperature of the eleventh zone is 185°C, the temperature of the twelfth zone is 195°C, and the temperature of the thirteenth zone is 190°C. The screw speed of the film blowing machine is 100rpm, the traction speed of the film blowing machine is 5m / min, and the blowing ratio of the film blowing machine is 2. After film blowing, the antibacterial high-barrier nano-cellulose-based composite film is obtained.

[0177] Figure 2 The infrared spectra of nanocellulose, sulfonated nanocellulose prepared in this example, and quaternary ammonium sulfonated nanocellulose are shown in Figure 1. In the infrared spectrum curve of nanocellulose, 3284 cm -1 The corresponding OH stretching vibration absorption peak is 1038 cm -1 The corresponding absorption peak is the stretching vibration of CO.

[0178] In the infrared spectrum of sulfonated nanocellulose, 1375 cm -1 and 896cm -1 The stretching vibration absorption peaks corresponding to O=S=O and COS of the sulfonic acid functional group respectively indicate that the sulfonic acid functional group is successfully connected to the molecular chain of nanocellulose.

[0179] In the infrared spectrum curve of quaternary ammonium sulfonated nanocellulose, the stretching vibration absorption peak of OH is from 3284 cm -1 Offset to 3359cm -1 This is because the electrostatic effect of the introduced quaternary ammonium functional groups changes the forces between hydrogen bonds in nanocellulose. In addition, 2905cm -1 and 2846cm -1 The asymmetric stretching vibration and symmetric stretching vibration absorption peaks of -CH2- in the molecular chain of octadecyltrimethylammonium chloride are 1433 cm -1 The corresponding peak is the stretching vibration absorption peak of the trimethyl functional group in the molecular chain of octadecyltrimethylammonium chloride, which indicates that octadecyltrimethylammonium chloride is successfully connected to the molecular chain of sulfonated nanocellulose.

[0180] Figure 3 The zeta potential diagram of nanocellulose, sulfonated nanocellulose prepared in this embodiment and quaternary ammonium sulfonated nanocellulose is shown in the figure. It can be seen that the surface charge of nanocellulose is -5.8mV, and the surface charge of sulfonated nanocellulose obtained after sulfonation modification is -11.5mV, which is due to the fact that more anionic sites are combined on the surface of nanocellulose after sulfonation modification. The surface charge of quaternary ammonium sulfonated nanocellulose obtained after quaternary ammonium modification is -2.7mV, which is due to the negative charge on the surface of sulfonated nanocellulose being neutralized by the positive charge of quaternary ammonium salt.

[0181] Figure 4 , Figure 5 and Figure 6 The infrared spectra of the chitosan used in this embodiment, the carboxymethyl chitosan prepared in this embodiment and the quaternized carboxymethyl chitosan are shown in FIG. Figure 4 In the infrared spectrum of chitosan shown in the figure, 1380cm -1The corresponding stretching vibration absorption peak of CN. Figure 5 In the infrared spectrum of carboxymethyl chitosan shown in the figure, 1601cm -1 and 1415cm -1 The antisymmetric and symmetric stretching vibration absorption peaks of the carboxymethyl functional group appeared at 1131 cm -1 and 1059cm -1 The stretching vibration absorption peak of COC appeared at , which indicated that the carboxymethyl functional group was successfully connected to the molecular chain of chitosan.

[0182] exist Figure 6 In the infrared spectrum of quaternized carboxymethyl chitosan shown in the figure, 1478 cm -1 The bending vibration absorption peak of CH of the quaternary ammonium functional group appeared at 1598 cm -1 The CN stretching vibration absorption peak of the quaternary ammonium functional group appeared at 1112 cm -1 and 1063cm -1 The stretching vibration absorption peak of the ether group CO appeared at , which indicated that the quaternary ammonium functional group was successfully connected to the molecular chain of carboxymethyl chitosan.

[0183] Figure 7 , Figure 8 and Fig. 9 The scanning electron micrographs of the chitosan used in this embodiment, the quaternized carboxymethyl chitosan prepared in this embodiment, and the silver-loaded chitosan are shown in FIG. Figure 7 It can be seen that the chitosan particles have a compact structure and a smooth surface. Figure 8 It can be seen that quaternized carboxymethyl chitosan has a relatively loose molecular structure, and its surface is mainly composed of stacked spherical particles. This is because the carboxymethyl functional groups and quaternary ammonium functional groups introduced into the chitosan molecules enhance the intramolecular interaction force, which is conducive to the large-space curling of its own double helix structure. Fig. 9 It can be seen that the surface of silver-loaded chitosan is rough, and a large number of silver nanoparticles are uniformly loaded on the chitosan.

[0184] Fig.10 and Fig.11 The transmission electron microscope images of the montmorillonite used in this embodiment and the intercalated montmorillonite prepared in this embodiment are shown in Figure 1. Compared with montmorillonite, the interlayer spacing of the intercalated montmorillonite is significantly increased, and the silver-loaded chitosan is evenly dispersed in the intercalated montmorillonite sheets. Fig.11 It is clear that silver nanoparticles are dispersed between the intercalated montmorillonite layers.

[0185] Fig.12The XRD spectra of silver-loaded chitosan, montmorillonite and intercalated montmorillonite prepared in this embodiment show that within the range of 2θ of 4 to 10°, silver-loaded chitosan has no obvious diffraction peak, while montmorillonite has obvious diffraction peaks within this angle range. According to the Bragg equation, the interlayer spacing of montmorillonite can be calculated to be 1.501nm. The characteristic diffraction peak of intercalated montmorillonite obtained after intercalation modification moves to 2θ=5.30°, and the interlayer spacing at this time increases from the initial 1.501nm to 1.665nm, which indicates that silver-loaded chitosan enters the interlamellar space of montmorillonite, increases the interlayer spacing of montmorillonite, and forms an intercalated composite material.

[0186] Example 2

[0187] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0188] (1) Nanocellulose powder was added to a sodium hydroxide solution with a mass fraction of 6 wt % (the ratio of nanocellulose powder to sodium hydroxide solution was 1 g:52 mL), and ultrasonic dispersion was performed at an ultrasonic power of 320 W for 38 min to obtain a nanocellulose dispersion. The nanocellulose dispersion was then mixed and stirred at 52 ° C for 4.5 h to obtain a nanocellulose suspension. 1,3-Propane sultone was dissolved in dimethyl sulfoxide to obtain a 1,3-Propane sultone solution with a mass fraction of 4.2 wt %, and the nanocellulose suspension was added. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.142, and the mixture was mixed and stirred at 62°C for 5.8 hours. After the reaction was completed, a reaction product was obtained, and a hydrochloric acid solution with a mass fraction of 6wt% was dripped into the reaction product to adjust its pH value to 1.8. The reaction product was then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 12000Da. After the dialysis was completed, the dialyzed product was placed at -62°C for freeze-drying for 11 hours to obtain sulfonated nanocellulose;

[0189] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:32 mL, and then ultrasonically dispersed for 38 min at an ultrasonic power of 320 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 0.8 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.2, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.22, and mixed and stirred at 62° C. for 3.8 h, and then heating was stopped, and mixed and stirred at room temperature for 13 h to obtain a reaction product, and then the reaction product was dialyzed for 5 days using a dialysis bag with a molecular weight cutoff of 12000 Da, and after the dialysis, the dialyzed product was freeze-dried at -42° C. for 21 h to obtain quaternary ammonium sulfonated nanocellulose;

[0190] (2) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:3.8, and ball-milled for 4.8 hours at a rotation speed of 520 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.2, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.55, and ball-milled for a second time at a rotation speed of 520 rpm for 5.8 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 8.5 wt % was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain the carboxymethyl chitosan;

[0191] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 12 g / L; add a 52 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 52° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.62, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 28 minutes under 52° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.05, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;

[0192] (3) under stirring, adding a sodium hydroxide solution with a mass fraction of 2.5 wt % to a silver nitrate solution with a mass fraction of 3.5 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.6, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 1.5 wt % dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;

[0193] The quaternized carboxymethyl chitosan obtained in step (2) is dispersed in deionized water to obtain a chitosan solution with a concentration of 12 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 72° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.62. After all the silver ammonia solution is dripped in, the mixture is stirred under heating in a water bath at 72° C. for 9.5 h. The reaction product is then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 12,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -42° C. for 21 h to obtain silver-loaded chitosan.

[0194] (4) dispersing the silver-loaded chitosan obtained in step (3) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 12 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4.2, mixing and stirring at 52° C. for 6.5 h, and then filtering, washing and drying to obtain intercalated montmorillonite;

[0195] (5) 75 parts of polylactic acid, 9 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 14 parts of intercalated montmorillonite obtained in step (4), 1.2 parts of epoxidized soybean oil, 0.7 parts of paraffin wax and 0.1 parts of antioxidant 1076 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 152° C., the temperature of the second zone is 162° C., the temperature of the third zone is 172° C., the temperature of the fourth zone is 178° C., the temperature of the fifth zone is 186° C., the temperature of the sixth zone is 191° C., the temperature of the seventh zone is 201° C., the temperature of the eighth zone is 196° C., the temperature of the die head is 182° C., and the screw speed is 220 rpm;

[0196] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 178°C, the temperature of the tenth zone is 182°C, the temperature of the eleventh zone is 188°C, the temperature of the twelfth zone is 198°C, and the temperature of the thirteenth zone is 192°C. The screw speed of the film blowing machine is 120rpm, the traction speed of the film blowing machine is 6m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the antibacterial high-barrier nano-cellulose-based composite film is obtained.

[0197] Example 3

[0198] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0199] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 7 wt % (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:55 mL), and ultrasonically disperse the nanocellulose powder for 35 min at an ultrasonic power of 350 W to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 55 ° C for 4 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 4.5 wt %. Add the nanocellulose suspension to the solution. 1,3-propane sultone solution was added, the mass ratio of nanocellulose powder in the nanocellulose suspension to 1,3-propane sultone was 1:0.145, and the mixture was mixed and stirred at 65°C for 5.5 hours. After the reaction was completed, a reaction product was obtained, and a hydrochloric acid solution with a mass fraction of 7wt% was dripped into the reaction product to adjust its pH value to 1.5. The reaction product was then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 15000Da. After the dialysis was completed, the dialyzed product was placed at -65°C for freeze-drying for 10 hours to obtain sulfonated nanocellulose;

[0200] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:35 mL, and then ultrasonically dispersed for 35 min at an ultrasonic power of 350 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.5, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.25, and mixed and stirred at 65° C. for 3.5 h, and then heating was stopped, and mixed and stirred at room temperature for 12 h to obtain a reaction product, and then the reaction product was dialyzed for 6 days using a dialysis bag with a molecular weight cutoff of 15000 Da, and after the dialysis, the dialyzed product was freeze-dried at -45° C. for 18 h to obtain quaternary ammonium sulfonated nanocellulose;

[0201] (2) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4, and ball-milled for 4.5 hours at a rotation speed of 550 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.5, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.6, and ball-milled for a second time at a rotation speed of 550 rpm for 5.5 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 9wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain the carboxymethyl chitosan;

[0202] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 15 g / L; add a 55 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 55° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.65, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 25 minutes under 55° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.1, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;

[0203] (3) under stirring, adding a sodium hydroxide solution with a mass fraction of 3 wt % to a silver nitrate solution with a mass fraction of 4 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.6, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 2 wt % dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;

[0204] The quaternized carboxymethyl chitosan obtained in step (2) is dispersed in deionized water to obtain a chitosan solution with a concentration of 15 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 75° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.65. After all the silver ammonia solution is dripped in, the mixture is stirred under heating in a water bath at 75° C. for 9 h. The reaction product is then dialyzed for 2 days using a dialysis bag with a molecular weight cutoff of 15,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -45° C. for 18 h to obtain silver-loaded chitosan.

[0205] (4) dispersing the silver-loaded chitosan obtained in step (3) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 15 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4.5, mixing and stirring at 55° C. for 6 h, and then filtering, washing and drying to obtain intercalated montmorillonite;

[0206] (5) 76 parts of polylactic acid, 8 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 13 parts of intercalated montmorillonite obtained in step (4), 2 parts of pentaerythritol, 0.5 parts of glyceryl monostearate and 0.5 parts of antioxidant DSTP are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 155° C., the temperature of the second zone is 165° C., the temperature of the third zone is 175° C., the temperature of the fourth zone is 180° C., the temperature of the fifth zone is 187° C., the temperature of the sixth zone is 192° C., the temperature of the seventh zone is 202° C., the temperature of the eighth zone is 197° C., the head temperature is 185° C., and the screw speed is 250 rpm;

[0207] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 180°C, the temperature of the tenth zone is 185°C, the temperature of the eleventh zone is 190°C, the temperature of the twelfth zone is 200°C, and the temperature of the thirteenth zone is 195°C. The screw speed of the film blowing machine is 150rpm, the traction speed of the film blowing machine is 7m / min, and the blowing ratio of the film blowing machine is 3. After film blowing, the antibacterial high-barrier nano-cellulose-based composite film is obtained.

[0208] Example 4

[0209] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0210] (1) Nanocellulose powder was added to a sodium hydroxide solution with a mass fraction of 8 wt % (the ratio of nanocellulose powder to sodium hydroxide solution was 1 g:58 mL), and ultrasonic dispersion was performed at an ultrasonic power of 380 W for 32 min to obtain a nanocellulose dispersion. The nanocellulose dispersion was then mixed and stirred at 58 ° C for 3.5 h to obtain a nanocellulose suspension. 1,3-Propane sultone was dissolved in dimethyl sulfoxide to obtain a 1,3-Propane sultone solution with a mass fraction of 4.8 wt %, and the nanocellulose suspension was added thereto. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.148, the mixture was mixed and stirred at 68°C for 5.2h, and a reaction product was obtained after the reaction was completed. A hydrochloric acid solution with a mass fraction of 8wt% was dripped into the reaction product to adjust the pH value thereof to 1.2, and then the reaction product was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 18000Da. After the dialysis was completed, the dialyzed product was placed at -68°C for freeze-drying for 8h to obtain sulfonated nanocellulose;

[0211] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:38 mL, and then ultrasonically dispersed for 32 min at an ultrasonic power of 380 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1.2 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 9.8, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.28, and mixed and stirred at 68° C. for 3.2 h, and then heating was stopped, and mixed and stirred at room temperature for 11 h to obtain a reaction product, and then the reaction product was dialyzed for 7 days using a dialysis bag with a molecular weight cutoff of 18000 Da, and after the dialysis, the dialyzed product was freeze-dried at -48° C. for 15 h to obtain quaternary ammonium sulfonated nanocellulose;

[0212] (2) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4.2, and ball-milled for 4.2 hours at a rotation speed of 580 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:3.8, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.65, and ball-milled for a second time at a rotation speed of 580 rpm for 5.2 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 9.5wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain the carboxymethyl chitosan;

[0213] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 18 g / L; add a dimethyl diallyl ammonium chloride solution with a mass fraction of 58 wt% to the carboxymethyl chitosan solution under continuous stirring and 58° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.68, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 22 minutes under 58° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.15, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;

[0214] (3) under stirring, adding a sodium hydroxide solution with a mass fraction of 3.5 wt % to a silver nitrate solution with a mass fraction of 4.5 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.7, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution with a concentration of 2.5 wt % dropwise to the silver oxide suspension until the black silver oxide precipitate is just completely dissolved, thereby obtaining a clear silver ammonia solution;

[0215] The quaternized carboxymethyl chitosan obtained in step (2) is dispersed in deionized water to obtain a chitosan solution with a concentration of 18 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 78° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.68. After all the silver ammonia solution is dripped in, the mixture is stirred under heating in a water bath at 78° C. for 8.5 h. The reaction product is then dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 18,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -48° C. for 15 h to obtain silver-loaded chitosan.

[0216] (4) dispersing the silver-loaded chitosan obtained in step (3) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 18 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:4.8, mixing and stirring at 58° C. for 5.5 h, and then filtering, washing and drying to obtain intercalated montmorillonite;

[0217] (5) 78 parts of polylactic acid, 8 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 12 parts of intercalated montmorillonite obtained in step (4), 1 part of polyvinyl alcohol, 0.8 parts of glyceryl distearate and 0.2 parts of antioxidant 168 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 158° C., the temperature of the second zone is 168° C., the temperature of the third zone is 178° C., the temperature of the fourth zone is 182° C., the temperature of the fifth zone is 188° C., the temperature of the sixth zone is 193° C., the temperature of the seventh zone is 203° C., the temperature of the eighth zone is 198° C., the temperature of the die head is 188° C., and the screw speed is 280 rpm;

[0218] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 182°C, the temperature of the tenth zone is 188°C, the temperature of the eleventh zone is 192°C, the temperature of the twelfth zone is 202°C, and the temperature of the thirteenth zone is 198°C. The screw speed of the film blowing machine is 180rpm, the traction speed of the film blowing machine is 8m / min, and the blowing ratio of the film blowing machine is 4. After film blowing, the antibacterial high-barrier nano-cellulose-based composite film is obtained.

[0219] Example 5

[0220] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. Figure 1 As shown, the preparation method specifically comprises the following steps:

[0221] (1) Add nanocellulose powder to a sodium hydroxide solution with a mass fraction of 10 wt % (the ratio of nanocellulose powder to sodium hydroxide solution is 1 g:60 mL), and ultrasonically disperse the nanocellulose at an ultrasonic power of 400 W for 30 min to obtain a nanocellulose dispersion. The nanocellulose dispersion is then mixed and stirred at 60 ° C for 3 h to obtain a nanocellulose suspension. Dissolve 1,3-propane sultone in dimethyl sulfoxide to obtain a 1,3-propane sultone solution with a mass fraction of 5 wt %. Add the nanocellulose suspension to the solution. A 1,3-propane sultone solution was added, the mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone was 1:0.15, the mixture was mixed and stirred at 70°C for 5 hours, and a reaction product was obtained after the reaction was completed. A 10wt% hydrochloric acid solution was dripped into the reaction product to adjust its pH value to 1, and then the reaction product was dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 20000Da. After the dialysis was completed, the dialyzed product was placed at -70°C for freeze-drying for 6 hours to obtain sulfonated nanocellulose;

[0222] The sulfonated nanocellulose was added to isopropanol in a ratio of 1 g:40 mL, and then ultrasonically dispersed for 30 min at an ultrasonic power of 400 W to obtain a sulfonated nanocellulose suspension, and a sodium hydroxide solution with a concentration of 1.5 mol / L was added dropwise to the sulfonated nanocellulose suspension to adjust its pH value to 10, and then octadecyltrimethylammonium chloride was added to the sulfonated nanocellulose suspension in a mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension of 1:0.3, and mixed and stirred at 70° C. for 3 h, and then heating was stopped, and mixed and stirred at room temperature for 10 h to obtain a reaction product, and then the reaction product was dialyzed for 8 days using a dialysis bag with a molecular weight cutoff of 20,000 Da, and after the dialysis, the dialyzed product was freeze-dried at -50° C. for 12 h to obtain quaternary ammonium sulfonated nanocellulose;

[0223] (2) chitosan powder and sodium hydroxide were mixed in a mass ratio of 1:4.5, and ball-milled for 4 hours at a speed of 600 rpm to obtain a mixture; then, sodium chloroacetate and sodium iodide were added to the mixture, the mass ratio of chitosan powder to sodium chloroacetate was 1:4, and the mass ratio of sodium chloroacetate to sodium iodide was 1:0.7, and ball-milled for a second time at a speed of 600 rpm for 5 hours to obtain a solid product; the solid product was mixed evenly with deionized water to obtain a product solution, and a hydrochloric acid solution with a mass fraction of 10 wt% was added to the product solution to adjust the pH value of the product solution to 7, and then the product solution was filtered, washed and dried to obtain the carboxymethyl chitosan;

[0224] Dissolve carboxymethyl chitosan in deionized water, mix well to obtain a carboxymethyl chitosan solution with a concentration of 20 g / L; add a 60 wt% dimethyl diallyl ammonium chloride solution to the carboxymethyl chitosan solution under continuous stirring and 60° C. water bath heating conditions, the mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:0.7, and after all the dimethyl diallyl ammonium chloride solution is added dropwise, continue to mix and stir for 20 minutes under 60° C. water bath heating conditions to obtain a reaction product; add acetone to the reaction product, the volume ratio of the reaction product to acetone is 1:1.2, and generate white floccules after mixing, and then filter, wash and dry to obtain quaternized carboxymethyl chitosan;

[0225] (3) under stirring, adding a sodium hydroxide solution with a mass fraction of 4 wt % to a silver nitrate solution with a mass fraction of 5 wt %, wherein the mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:0.8, and reacting to generate a silver oxide suspension containing a black silver oxide precipitate, and adding a 3 wt % ammonia solution to the silver oxide suspension until the black silver oxide precipitate is completely dissolved, thereby obtaining a clear silver ammonia solution;

[0226] The quaternized carboxymethyl chitosan obtained in step (2) is dispersed in deionized water to obtain a chitosan solution with a concentration of 20 g / L. The silver ammonia solution is dripped into the chitosan solution under stirring and heating in a water bath at 80° C., wherein the mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:0.7. After all the silver ammonia solution is dripped in, the mixture is stirred under heating in a water bath at 80° C. for 8 h. The reaction product is then dialyzed for 3 days using a dialysis bag with a molecular weight cutoff of 20,000 Da. After the dialysis is completed, the dialyzed product is freeze-dried at -50° C. for 12 h to obtain silver-loaded chitosan.

[0227] (4) dispersing the silver-loaded chitosan obtained in step (3) in deionized water to obtain a silver-loaded chitosan solution with a concentration of 20 g / L, adding montmorillonite to the silver-loaded chitosan solution, wherein the mass ratio of the silver-loaded chitosan to the montmorillonite in the silver-loaded chitosan solution is 1:5, mixing and stirring at 60° C. for 5 h, and then filtering, washing and drying to obtain intercalated montmorillonite;

[0228] (5) 78 parts of polylactic acid, 8 parts of quaternary ammonium sulfonated nanocellulose obtained in step (1), 12 parts of intercalated montmorillonite obtained in step (4), 1 part of triacetin, 0.5 parts of zinc stearate and 0.5 parts of antioxidant 691 are mixed uniformly to obtain a mixture, and the mixture is fed into a screw extruder for melt extrusion, wherein the temperature of the first zone in the barrel of the screw extruder is 160°C, the temperature of the second zone is 170°C, the temperature of the third zone is 180°C, the temperature of the fourth zone is 185°C, the temperature of the fifth zone is 190°C, the temperature of the sixth zone is 195°C, the temperature of the seventh zone is 205°C, the temperature of the eighth zone is 200°C, the temperature of the die head is 190°C, and the screw speed is 300 rpm;

[0229] After screw extrusion, cooling and pelletizing, the composite masterbatch is obtained, and the composite masterbatch is sent to a film blowing machine for film blowing. The temperature of the ninth zone in the barrel of the film blowing machine is 185°C, the temperature of the tenth zone is 190°C, the temperature of the eleventh zone is 195°C, the temperature of the twelfth zone is 205°C, and the temperature of the thirteenth zone is 200°C. The screw speed of the film blowing machine is 200rpm, the traction speed of the film blowing machine is 10m / min, and the blowing ratio of the film blowing machine is 5. After film blowing, the antibacterial high-barrier nano-cellulose-based composite film is obtained.

[0230] Example 6

[0231] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Example 1 is that in step (1), the mass ratio of nanocellulose powder to 1,3-propane sultone in the nanocellulose suspension is adjusted to 1:0.13, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0232] Example 7

[0233] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Example 1 is that in step (1), the mass ratio of nanocellulose powder to 1,3-propane sultone in the nanocellulose suspension is adjusted to 1:0.16, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0234] Example 8

[0235] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Example 1 is that in step (1), the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is adjusted to 1:0.1, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0236] Example 9

[0237] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Example 1 is that in step (1), the mass ratio of sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is adjusted to 1:0.4, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0238] Example 10

[0239] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Example 1 is that in step (3), the mass ratio of quaternized carboxymethyl chitosan to silver nitrate is adjusted to 1:0.5, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0240] Embodiment 11

[0241] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Example 1 is that in step (3), the mass ratio of quaternized carboxymethyl chitosan to silver nitrate is adjusted to 1:0.8, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0242] Example 12

[0243] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Embodiment 1 is that in step (4), the mass ratio of silver-loaded chitosan to montmorillonite in the silver-loaded chitosan solution is adjusted to 1:3, and the other process parameters and operation steps are exactly the same as those in Embodiment 1.

[0244] Embodiment 13

[0245] This embodiment provides a method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables. The difference from Example 1 is that in step (4), the mass ratio of silver-loaded chitosan to montmorillonite in the silver-loaded chitosan solution is adjusted to 1:6, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0246] Comparative Example

[0247] This comparative example provides a method for preparing a composite film. The difference from Example 1 is that steps (1) to (4) are omitted, quaternary ammonium sulfonated nanocellulose and intercalated montmorillonite are not added to the mixed material, and the weight proportions of the other components are as follows:

[0248] Polylactic acid 97 parts;

[0249] 1 part of ethylene glycol;

[0250] 1.5 parts of calcium stearate;

[0251] Antioxidant 10100.5 parts;

[0252] Other process parameters and operation steps are exactly the same as those in Example 1.

[0253] Application Examples

[0254] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on green vegetables. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other cartons. Two bunches of green vegetables with similar freshness and the same weight were placed in the two cartons respectively and sealed, and stored at 5°C. The condition of the green vegetables was observed and photographed every two days. Fig.17As shown, by comparison, it can be seen that the use of the composite film provided in Example 1 of the present invention to preserve and store green vegetables can keep the green vegetables extremely fresh on the 8th day of storage, effectively inhibit the water loss of the green vegetables, maintain the color of the green vegetables, maintain the quality during storage, and extend the shelf life.

[0255] The composite films provided in Example 1 and the comparative example were used to carry out a fresh-keeping storage experiment on mangoes. Two identical cartons were prepared, and the composite film provided in Example 1 was pasted on the inner wall of one of the cartons, and the composite film provided in the comparative example was pasted on the inner wall of the other carton. Two mangoes of similar freshness and weight were placed in the two cartons respectively and sealed, and stored at 5°C. The state of the mangoes was observed and photographed every two days, as shown in FIG. Fig.18 As shown, by comparison, it can be seen that the use of the composite film provided in Example 1 of the present invention to preserve and store mangoes can keep the mangoes extremely fresh on the 10th day of storage, effectively inhibit the mangoes from losing water, rotting and deteriorating, maintain their quality during storage, and extend their shelf life.

[0256] The mechanical properties, barrier properties and antibacterial properties of the composite films prepared in Examples 1-13 and the comparative example were tested, and the testing method was as follows:

[0257] (1) Mechanical properties: The mechanical properties of the composite films were characterized by tensile strength and elongation at break. The tensile strength and elongation at break of the composite films provided in Examples 1 to 13 and the comparative example were measured using a tensile testing machine, and the tensile rate was set to 50 mm / min.

[0258] (2) Barrier property: The barrier property of the composite films provided in Examples 1-13 and the comparative example was characterized by water vapor permeability. The water vapor permeability was measured in a constant temperature and humidity chamber in accordance with GB / T 1037-2021 "Determination of water vapor permeability of plastic films and sheets - Cup weight gain and weight loss method". The experimental conditions were: temperature 38±0.6°C, relative humidity 90%±2%.

[0259] (3) Antibacterial properties:

[0260] The antibacterial properties of the composite films provided in Example 1 and the comparative example were analyzed by the antibacterial zone method. The composite films provided in Example 1 and the comparative example were first cut into discs with a diameter of 6 mm and uniform size. Then 100 μL of a 10 6CFU / mL of Escherichia coli suspension (model D1125B, purchased from Shanghai Roadway Technology Co., Ltd., China) and Staphylococcus aureus suspension (model E2528B, purchased from Shanghai Roadway Technology Co., Ltd., China) were evenly spread on the surface of the nutrient agar medium plate. The cut film samples were placed on the surface of the nutrient agar medium plate coated with the bacterial solution, and then placed in a 37℃ constant temperature box for 24 hours. The size of the antibacterial zone around the film sample was observed and photographed and recorded, and the following was obtained: Fig.13 , Fig.14 , Fig.15 and Fig.16 Colony images are shown.

[0261] Fig.13 and Fig.14 The colony images of the composite films prepared in the comparative example and embodiment 1 respectively were obtained in the antibacterial performance test of Escherichia coli. It can be seen from the comparison that there is almost no antibacterial zone around the composite film prepared in the comparative example, while there is an obvious antibacterial zone around the composite film prepared in embodiment 1. The diameter of the antibacterial zone is about 19 mm after measurement, which indicates that the composite film prepared in the present invention has excellent antibacterial ability against Escherichia coli.

[0262] Fig.15 and Fig.16 The colony images of the composite films prepared in the comparative example and Example 1 of the present invention respectively obtained in the antibacterial performance test of Staphylococcus aureus. It can be seen from the comparison that there is almost no antibacterial zone around the composite film prepared in the comparative example, and there is an obvious antibacterial zone around the composite film prepared in Example 1. After measurement, the diameter of the antibacterial zone is about 18 mm, which indicates that the composite film prepared in the present invention has excellent antibacterial ability against Staphylococcus aureus.

[0263] (4) Antibacterial properties:

[0264] The antibacterial activity of the composite films provided in Examples 1-13 was analyzed by colony counting method. The composite films provided in Examples 1-13 and the comparative example were cut into 3 mm×3 mm square film samples. 100 μL of 10 6 CFU / mL of Escherichia coli suspension (model D1125B, purchased from Shanghai Roadway Technology Co., Ltd., China) and Staphylococcus aureus suspension (model E2528B, purchased from Shanghai Roadway Technology Co., Ltd., China) were dispersed on the surface of the film sample and cultured at 37°C for 12 hours to obtain the sample; then 1500μL of PBS solution was used to wash the bacteria from the sample surface, and 20μL of PBS solution was taken and dispersed on the nutrient agar plate, and cultured at 37°C for 12 hours, after which the surviving colonies were counted. The antibacterial rate (%) was calculated using the following formula:

[0265]

[0266] Wherein, X is the number of colonies on the composite film sample provided in the comparative example, and Y is the number of colonies on the composite film sample provided in Examples 1-13.

[0267] Table 1

[0268] Tensile strength MPa Elongation at break % <![CDATA[Water vapor transmission rate g / (m 2 ·24h)]]> Escherichia coli antibacterial rate% Antibacterial rate of Staphylococcus aureus % Example 1 63.5 252.3 10.2 97.2 96.5 Example 2 64.8 249.6 9.7 97.9 96.8 Example 3 67.2 245.8 9.3 98.8 97.3 Example 4 70.9 237.9 8.5 99.7 98.7 Example 5 68.6 240.5 8.8 99.5 98.2 Example 6 43.3 193.4 18.3 82.6 78.1 Example 7 50.4 182.3 13.2 84.0 80.2 Example 8 47.8 186.1 15.8 78.5 74.8 Example 9 52.6 177.2 12.6 86.4 82.3 Example 10 60.9 158.7 11.5 72.9 70.5 Embodiment 11 56.2 170.4 10.7 90.3 86.7 Example 12 62.4 143.8 28.9 96.1 97.3 Embodiment 13 59.0 164.9 16.1 75.2 72.6 Comparative Example 32.3 78.2 52.6 — —

[0269] It can be seen from the test data provided in Table 1 that the composite films provided in Examples 1-5 of the present invention have excellent mechanical properties, barrier properties and antibacterial properties.

[0270] It can be seen from the test data of Example 1, Example 6 and Example 7 that too high or too low a dosage of 1,3-propane sultone will directly affect the sulfonation modification effect of nanocellulose and the subsequent quaternization modification effect, thereby affecting the mechanical properties, barrier properties and antibacterial properties of the composite film.

[0271] It can be seen from the test data of Example 1, Example 8 and Example 9 that too high or too low an amount of octadecyltrimethylammonium chloride will directly affect the quaternary ammonium modification effect on nanocellulose, thereby affecting the mechanical properties, barrier properties and antibacterial properties of the composite film.

[0272] It can be seen from the test data of Example 1, Example 10 and Example 11 that excessively high or low dosage of silver nitrate directly affects the loading amount of silver nanoparticles in the silver-loaded chitosan, thereby affecting the antibacterial properties of the composite film.

[0273] It can be seen from the test data of Example 1, Example 12 and Example 13 that too high or too low a dosage of montmorillonite directly affects the intercalation modification effect of montmorillonite, and further affects the barrier properties of the composite film.

[0274] It can be seen from the test data of Example 1 and the comparative example that the present invention can significantly improve the mechanical properties, barrier properties and antibacterial properties of the polylactic acid composite film by adding quaternary ammonium sulfonated nanocellulose and intercalated montmorillonite to the composite film.

[0275] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing an antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables, characterized in that: The preparation method comprises: (I) sulfonating and modifying nanocellulose powder with 1,3-propane sultone to obtain sulfonated nanocellulose; then quaternizing and modifying the sulfonated nanocellulose with octadecyltrimethylammonium chloride to obtain quaternary ammonium sulfonated nanocellulose; (II) ball-milling chitosan powder and sodium hydroxide to obtain a mixture, adding sodium chloroacetate and sodium iodide to the mixture for a second ball-milling to obtain carboxymethyl chitosan; then, quaternizing the carboxymethyl chitosan with dimethyl diallyl ammonium chloride to obtain quaternized carboxymethyl chitosan; (III) dispersing the quaternized carboxymethyl chitosan obtained in step (II) in deionized water to obtain a chitosan solution, dripping a silver ammonia solution into the chitosan solution under stirring and water bath heating conditions, and continuing to mix, stir and heat to react after all the silver ammonia solution has been dripped in, and then dialyzing and freeze-drying to obtain silver-loaded chitosan; (IV) dispersing the silver-loaded chitosan obtained in step (III) in deionized water to obtain a silver-loaded chitosan solution, adding montmorillonite to the silver-loaded chitosan solution, mixing, stirring and heating, and then filtering, washing and drying to obtain intercalated montmorillonite; (V) Polylactic acid, the quaternary ammonium sulfonated nanocellulose obtained in step (I), the intercalated montmorillonite obtained in step (IV), a plasticizer, a lubricant and an antioxidant are uniformly mixed to obtain a mixture, and the mixture is sequentially melt-extruded, cooled, pelletized and film-blown to obtain the antibacterial high-barrier nanocellulose-based composite film.

2. The preparation method according to claim 1, characterized in that: In step (I), the sulfonated nanocellulose is prepared by the following method: The nanocellulose powder is added to a sodium hydroxide solution, and a nanocellulose dispersion is obtained after ultrasonic dispersion, and then the nanocellulose dispersion is mixed, stirred and heated to obtain a nanocellulose suspension; a 1,3-propane sultone solution is added to the nanocellulose suspension, and the mixture is mixed, stirred and heated to react, and a reaction product is obtained after the reaction is completed, a hydrochloric acid solution is dripped into the reaction product to adjust the pH value thereof, and then the reaction product is dialyzed and freeze-dried to obtain the sulfonated nanocellulose; The mass fraction of the sodium hydroxide solution is 5-10wt%; The ratio of the nanocellulose powder to the sodium hydroxide solution is 1 g: (50-60) mL; The ultrasonic power of the ultrasonic dispersion of the nanocellulose powder and the sodium hydroxide solution is 300-400W; The ultrasonic dispersion time of the nanocellulose powder and the sodium hydroxide solution is 30 to 40 minutes; The mixing and stirring time of the nanocellulose dispersion is 3 to 5 hours; The heating temperature of the nanocellulose dispersion during mixing and stirring is 50-60°C; The 1,3-propane sultone solution consists of 1,3-propane sultone and dimethyl sulfoxide; The mass fraction of 1,3-propane sultone in the 1,3-propane sultone solution is 4-5wt%; The mass ratio of the nanocellulose powder in the nanocellulose suspension to the 1,3-propane sultone is 1:(0.14-0.15); The mixing and stirring time of the nanocellulose suspension and 1,3-propane sultone is 5 to 6 hours; The heating temperature when the nanocellulose suspension and 1,3-propane sultone are mixed and stirred is 60-70°C; The mass fraction of the hydrochloric acid solution is 5-10wt%; Adding hydrochloric acid solution dropwise into the reaction product to adjust the pH value thereof to 1-2; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 2 to 3 days; The freeze drying temperature is -60 to -70°C; The freeze-drying time is 6 to 12 hours.

3. The preparation method according to claim 1, characterized in that: In step (I), the quaternary ammonium sulfonated nanocellulose is prepared by the following method: The sulfonated nanocellulose is added to isopropanol to obtain a sulfonated nanocellulose suspension after ultrasonic dispersion, an alkali solution is added dropwise to the sulfonated nanocellulose suspension to adjust its pH value, octadecyltrimethylammonium chloride is then added to the sulfonated nanocellulose suspension, mixed and stirred, and heated for a period of time, then the heating is stopped, and the mixing and stirring is continued at room temperature for a period of time to obtain a reaction product, and the reaction product is dialyzed and freeze-dried to obtain the quaternary ammonium sulfonated nanocellulose; The ratio of the sulfonated nanocellulose to isopropanol is 1 g: (30-40) mL; The ultrasonic power of the ultrasonic dispersion of the sulfonated nanocellulose and isopropanol is 300-400W; The ultrasonic dispersion time of the sulfonated nanocellulose and isopropanol is 30 to 40 minutes; The concentration of the alkali solution is 0.5-1.5 mol / L; Adding alkaline solution dropwise to the sulfonated nanocellulose suspension to adjust the pH value thereof to 9-10; The mass ratio of the sulfonated nanocellulose to octadecyltrimethylammonium chloride in the sulfonated nanocellulose suspension is 1:(0.2-0.3); The mixing time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride is 3 to 4 hours; The heating temperature when the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride are mixed and stirred is 60-70°C; The mixing and stirring time of the sulfonated nanocellulose suspension and octadecyltrimethylammonium chloride at room temperature is 10 to 15 hours; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 5 to 8 days; The freeze drying temperature is -40 to -50°C; The freeze-drying time is 12 to 24 hours.

4. The preparation method according to claim 1, characterized in that: In step (II), the mass ratio of the chitosan powder to sodium hydroxide is 1:(3.5-4.5); The rotation speed of the first ball mill is 500-600 rpm; The time of the first ball milling is 4 to 5 hours; The mass ratio of the chitosan powder to sodium chloroacetate is 1:(3-4); The mass ratio of the sodium chloroacetate to the sodium iodide is 1:(0.5-0.7); The rotation speed of the secondary ball milling is 500-600 rpm; The secondary ball milling time is 5 to 6 hours; The preparation process of the carboxymethyl chitosan also includes: After the secondary ball milling, a solid product is obtained, and the solid product is mixed evenly with deionized water to obtain a product solution. A hydrochloric acid solution with a mass fraction of 8-10wt% is added to the product solution to adjust the pH value of the product solution to 7; then, the product solution is filtered, washed and dried to obtain the carboxymethyl chitosan.

5. The preparation method according to claim 1, characterized in that: In step (II), the quaternized carboxymethyl chitosan is prepared by the following method: The carboxymethyl chitosan is dissolved in deionized water and mixed evenly to obtain a carboxymethyl chitosan solution; under continuous stirring and water bath heating conditions, a dimethyl diallyl ammonium chloride solution is added dropwise to the carboxymethyl chitosan solution, and after the dimethyl diallyl ammonium chloride solution is completely added dropwise, the mixture is continuously stirred and heated to obtain a reaction product; acetone is added to the reaction product, and white floccules are generated after mixing, and then suction filtration, washing and drying are performed to obtain the quaternized carboxymethyl chitosan; The concentration of carboxymethyl chitosan in the carboxymethyl chitosan solution is 10-20 g / L; The mass fraction of the dimethyldiallylammonium chloride solution is 50-60wt%; During the dropwise addition of the dimethyldiallylammonium chloride solution, the water bath heating temperature is 50-60° C.; The mass ratio of carboxymethyl chitosan in the carboxymethyl chitosan solution to dimethyl diallyl ammonium chloride in the dimethyl diallyl ammonium chloride solution is 1:(0.6-0.7); After all the dimethyldiallylammonium chloride solution has been added dropwise, continue to mix and stir under heating in a water bath for 20 to 30 minutes; The volume ratio of the reaction product to the acetone is 1:(1-1.2).

6. The preparation method according to claim 1, characterized in that: In step (III), the concentration of quaternized carboxymethyl chitosan in the chitosan solution is 10-20 g / L; The silver ammonia solution is prepared by the following method: Under stirring conditions, adding a sodium hydroxide solution to the silver nitrate solution to react and generate a silver oxide suspension containing a black silver oxide precipitate, and adding an ammonia solution dropwise to the silver oxide suspension until the black silver oxide precipitate is completely dissolved to obtain a clear silver ammonia solution; The mass fraction of the silver nitrate solution is 3-5wt%; The mass fraction of the sodium hydroxide solution is 2-4wt%; The mass ratio of the silver nitrate in the silver nitrate solution to the sodium hydroxide in the sodium hydroxide solution is 1:(0.5-0.8); The concentration of the ammonia solution is 1-3 wt %; During the dropwise addition of the silver ammonia solution, the water bath is heated at a temperature of 70-80° C. The mass ratio of the quaternized carboxymethyl chitosan to silver nitrate is 1:(0.6-0.7); After all the silver ammonia solution has been dripped in, continue mixing and stirring for 8 to 10 hours; The molecular weight cut-off of the dialysis bag used in the dialysis is 10000~20000Da; The dialysis time is 2 to 3 days; The freeze drying temperature is -40 to -50°C; The freeze-drying time is 12 to 24 hours.

7. The preparation method according to claim 1, characterized in that: In step (IV), the concentration of silver-loaded chitosan in the silver-loaded chitosan solution is 10-20 g / L; The mass ratio of the silver-loaded chitosan in the silver-loaded chitosan solution to the montmorillonite is 1:(4-5); The mixing and stirring time of the silver-loaded chitosan solution and montmorillonite is 5 to 7 hours; The heating temperature when the silver-loaded chitosan solution and montmorillonite are mixed and stirred is 50-60°C.

8. The preparation method according to claim 1, characterized in that: In step (V), the weight proportions of the components in the mixed material are as follows: Polylactic acid 75-78 parts; 8-10 parts of quaternary ammonium sulfonated nanocellulose; Intercalated montmorillonite 12-14 parts; 1~2 parts of plasticizer; Lubricant 0.5~1.5 parts; Antioxidant 0.1~0.5 parts; The plasticizer includes any one of triacetin, tributyl citrate, dibutyl phthalate, ethylene glycol, propylene glycol, sorbitol, pentaerythritol, acetyl tributyl citrate, epoxy soybean oil, propylene glycol adipate polyester, dioctyl maleate, polyethylene glycol or polyvinyl alcohol, or a combination of at least two thereof; The lubricant includes any one of paraffin, zinc stearate, calcium stearate, glyceryl monostearate or glyceryl distearate, or a combination of at least two thereof; The antioxidant includes any one of antioxidant 1010, antioxidant 1076, antioxidant 300, antioxidant 1790, antioxidant DSTP, antioxidant 1098, antioxidant 168 or antioxidant 691, or a combination of at least two thereof.

9. The preparation method according to claim 1, characterized in that: In step (V), the melt extrusion process is carried out in a screw extruder, and the barrel of the screw extruder is divided into a first zone, a second zone, a third zone, a fourth zone, a fifth zone, a sixth zone, a seventh zone and an eighth zone with different temperatures along the material flow direction; The temperature of the first zone is 150-160°C; The temperature of the second zone is 160-170°C; The temperature of the third zone is 170-180°C; The temperature of the fourth zone is 175-185°C; The temperature of the fifth zone is 185-190°C; The temperature of the sixth zone is 190-195°C; The temperature of the seventh zone is 200-205°C; The temperature of the eighth zone is 195-200°C; The head temperature of the screw extruder is 180-190°C; The screw speed of the screw extruder is 200-300 rpm; The film blowing process is carried out in a film blowing machine, and the inside of the barrel of the film blowing machine is divided into a ninth zone, a tenth zone, an eleventh zone, a twelfth zone and a thirteenth zone with different temperatures along the material flow direction; The temperature of the ninth zone is 175-185°C; The temperature of the tenth zone is 180-190°C; The temperature of the eleventh zone is 185-195°C; The temperature of the twelfth zone is 195-205°C; The temperature of the thirteenth zone is 190-200°C; The screw speed of the film blowing machine is 100-200 rpm; The traction speed of the film blowing machine is 5-10 m / min; The blowing ratio of the film blowing machine is 2-5.

10. An antibacterial high-barrier nanocellulose-based composite film for preserving fruits and vegetables prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The antibacterial high-barrier nano-cellulose-based composite film comprises polylactic acid, quaternary ammonium sulfonated nano-cellulose, intercalated montmorillonite, a plasticizer, a lubricant and an antioxidant.

Citation Information

Patent Citations

  • Silver-loaded chitosan-based phyllosilicate nanocomposite material and preparation method and application thereof

    CN102585302A

  • Preparation method based on amphoteric cellulose composite material

    CN103480344A

  • Biodegradable modified polylactic acid membrane and preparation method thereof

    CN108707324A

  • Quaternary ammonium-sulfonation microcrystalline cellulose stabilizer and application of stabilizer to cellular herbicides

    CN109575144A

  • Fully biodegradable multi-component film material and preparing method thereof

    WO2011079492A1

Cited By

  • Degradable environment-friendly packaging material and preparation process thereof

    CN119842198A